Structure-based virtual screening identifies dicoumarol as a potent InhA inhibitor against Nocardia seriolae infection in largemouth bass (Micropterus salmoides) - Jin-Lai Gu; Chen-Wang Lu; Lin-Feng Kuang; Jie He; Zheng-Ran Jian; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Zheng-Yang Zhou; Ming-Zhu Liu; Peng-Fei Li; Er-Long Wang; et al. (Aquaculture, 2027)

Tensile strength characteristics of unsaturated Hunan clay - Gaoliang Tao; Song Chen; Qing-sheng Chen; Wenxing Tang; Zhe Huang; Ziyue Li; Sanjay Nimbalkar (European Journal of Environmental and Civil Engineering, 2026)

Association of structural characteristics with immunostimulatory activity of pectic polysaccharides prepared from Tartary buckwheat sprouts by enzymatic degradation and partial acid hydrolysis - Lin Zhang; Bo Li; Xuan Gao; Mao-Qing Wang; Ya-Nan Cao; Mao-Ling Tan; Yi-Chen Hu; Liang Zou; Dan Li; Yong Deng; Jing-Wei Huang; Ding-Tao Wu (Food Research International, 2026)

F-doped FeNC catalyst with axial ligand engineering: breaking the strong adsorption barrier for efficient non-radical peroxymonosulfate (PMS) activation and antibiotic removal - Yuxuan Lv; Xiaoyu Shao; Yang Tao; Liang Ouyang; Zekang Li; Qing Fu; Sanying Hou (Environmental Research, 2026)

Photoexcited directional charge transfer channels on iron-doped bismuth oxybromide for efficient peroxymonosulfate activation in water treatment - Kai Teng; Yi Tao; Mengwei Wu; Chang Liu; YeFei Su; Jiangjun Lin; Qing Qu; Lei Li (Journal of Environmental Chemical Engineering, 2026)

A compost-derived functional microbial consortium fortifies humification during bio-organic fertilizer production - Yang Yang; Yuxin Sun; Jiaqi Liu; Xueqing Jia; Tao Wang; Qing Chen; Yanming Li; Yuyun Wang; Zhi Xu; Yuquan Wei; RuiXue Chang (Journal of Environmental Chemical Engineering, 2026)

Microbial and environmental determinants of 1-propanol biosynthesis in Jiang-flavor Baijiu fermentation - Wei-Tao Zhai; Han Zhao; Li-Juan Chai; Wei Zhang; Xiao-Juan Zhang; Zhen-Ming Lu; Chuan-Qiang Gao; Guan-Ru Si; Wen-Qing Zhang; Song-Tao Wang; Cai-Hong Shen; Zheng-Hong Xu (Food Microbiology, 2026)

A dynamic point-association graph method for surface settlement prediction in subway foundation pits: application to Daqiao Station - Tao Kong; Zhen-hua Yang; Qing Tan; Zhao-cheng Liu; Ke Liu; Chuan-dong Yao; Zhen-long Xue; Yu-heng Li (Applied Geophysics, 2026)

A new dipeptide from entomogenous fungus Metapochonia suchlasporia Y9 - Hong-Yan Yang; Jia-Qian Yang; Zhi-Pu Huang; Ke-Tao Zhang; Xin-Yi Chen; Jin-Li Zhao; Yan Wang; Qing Zhao; Xiao-Mei Zhang (Natural Product Research, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Oak fossils reveal a cooler climate in northern Thailand during the late Oligocene–Early Miocene - Napussawan Thongsangtum; Jian Huang; Yupa Thasod; Yi-Qing Gu; Nguyen Ba Hung; Shu-Feng Li; Tao Su (Geobios, 2026)

Dual-functional quaternized chitosan-modified carbon dots within a polymeric fiber-gel scaffold for infected wound healing - Yuanyuan Geng; Fangman Chen; Yanteng Xu; Xiaowei Hao; Chenxi Ye; Enguo Ju; Haixia Wang; Yu Tao; Mingqiang Li; Yi Wang; Qing Yuan (Carbohydrate Polymers, 2026)

An Indicator System for Evaluating the Powerhouse of Meteorological Science and Technology: Design and Preliminary Application - Chaolin Zhang; Xudong Liang; Min Wen; Jianjun He; Wenjuan Zhang; Chang Liu; Qing Sun; Rong Yu; Xiaolu Yan; Zhu Zhang; Qihua Jin; Aili Shi; et al. (Journal of Meteorological Research, 2026)

Amifostine alleviates ionizing radiation-induced small intestinal motility dysfunction in mice by remodeling the structure of the enteric nervous system - Sha-Sha Tao; Yan Li; Fei Li; Yan Wang; Meng-Ying Li; Qian Zhang; Yun-Qing Li (Histochemistry and Cell Biology, 2026)

Study on the present-day crustal deformation characteristics and mechanism of the Yangyuan basin - Chen Gao; Jun Cao; Jian-Bao Sun; Jiang-Tao Qiu; Guang-Qing Ma; Fan Li (Applied Geophysics, 2026)

Single-cell sequencing reveals the co-option of epithelial structural programs by macrophages in teleost granulomas - Zhengyang Zhou; Jinlai Gu; Zhengran Jian; Jie He; Zhendong Zhong; Quanxin Xiong; Min Qi; Yuanchang Gao; Sheng Lian; Shangjie Bai; Chenwang Lu; Linfeng Kuang; et al. (Aquaculture, 2026)

IL-8-expressing recombinant Bacillus subtilis: A novel immunostimulant for improving production efficiency and disease resilience in Sebastes schlegelii aquaculture - Qing Yang; Hong-Yu Jiang; Ming-Tao Li; Bin-Tong Yang; Shu Li; Wei Cong; Yuan-Huan Kang (Aquaculture, 2026)

Withanolides from Datura stramonium: two unprecedented B-ring-seco derivatives and anti-inflammatory active analogues - Juan Pan; Gang-Tao Bu; Si-Yi Wang; Jia-Tong Wu; Meng-Meng Li; Wei Guan; Qing-Shan Chen; Li-Li Zhang; Xiao-Chi Ma; Hai-Xue Kuang; Yan Liu (Phytochemistry, 2026)

Application of lauroyl arginate ethyl to control Listeria monocytogenes biofilms and cross-contamination via domestic kitchen surfaces - Kenan Zhang; Bingran Zhang; Qing Li; Yaqi Wang; Jingyue Liu; Tao Yu; Yiping Zhang; Xiaobing Jiang (Food Research International, 2026)

Cellular copper overload mediates senescence-associated secretory phenotype induction in BV2 microglia following lead and copper exposure - Tao Wang; Chao Chen; Ran Li; Li-Hong Su; Hao-Jie Tian; Hui-Jing Wang; Jia-Yi Xiong; Qing Dai; Di Wu; Gang Zheng (Food and Chemical Toxicology, 2026)

A layered approach to secure the safety and therapeutic efficacy of hiPSC-derived functionalized neuronal tissueoid for repair after complete spinal cord lnjury in rats - Qing-shuai Wei; Quan-ying Xing; Yuan-huan Ma; Ke-jun Zhang; Wen-tao Ma; Mei-ling Zhang; Hui-juan Shi; Li-zhi Peng; Jun-hua Wang; Qi-xing Hu; Hou-ge Li; Ying Liu; et al. (Chemical Engineering Journal, 2026)

The role of oxygen vacancies and metallic Ru in regulating oxide pathway mechanism for acidic water electrolysis - Dinghua Zhou; Yutian Ding; Tao Song; Jiayi Wu; Zengyu Su; Zhiyong Fang; Muhammad Bilal Hussain; Peili Zhang; Xian-Zhu Fu; Shao-Qing Liu; Shuwen Wu; Jing-Li Luo (Chemical Engineering Journal, 2026)

Impact of tropical cyclone intensity evolution under different tracks on ozone in the Pearl River Delta, China - Shanshan Ouyang; Tao Deng; Chunhui Li; Jingyang Chen; Guowen He; Xue Zhang; Qing Wang; Zebiao Zhang; Gongke Rao (Atmospheric Research, 2026)

Pre-Harvest Continuous Led Lighting Improves Nutritional Quality and Sugar Accumulation in Hydroponic Lettuce - Li Zhang; Qiqi Zhang; Tao Huang; Hui Jiang; Bo Song; Chaohua Sun; Qing Qin; Yuejian Li; Qichang Yang; Xiao Yang; Hongyuan Song (Journal of Plant Growth Regulation, 2026)

Sustained Intra-Articular Delivery of Triple Therapeutics Using a Phase-Transition Phospholipid-Based Gel for Effective Treatment of Gouty Arthritis - Sirui Ma; Jing Yang; Ao Li; Qing Lin; Tao Gong (Pharmaceutical Research, 2026)

A novel UAV-based fusion of spectral and textural features with canopy stratification for accurate estimation of vertical nitrogen distribution in cotton - Guldana Sarsen; Qiu-xiang Tang; Ya-bin Li; Long-long Bao; Yu-hang Xu; Guang-yun Sun; Jian-wen Wu; Yierxiati Abulaiti; Qing-qing Lv; Fubin Liang; Na Zhang; Ren-song Guo; et al. (Computers and Electronics in Agriculture, 2026)

Revealing the roles of biochar in anaerobic digestion of waste activated sludge with the overloading accumulation of humic acids - Wen-Tao Li; Fei Wang; Qing-Bin Meng; Sheng-Jie Sun; Cong-Cong Tang; Lei Yang; Jun Lan; Ai-Juan Zhou; Wenzong Liu; Yong-Xiang Ren; Zhang-Wei He (Journal of Water Process Engineering, 2026)

Single-cell sequencing reveals metabolic reprogramming and immune regulation underlie the maintenance of teleost granulomas - Zheng-Yang Zhou; Zheng-Ran Jian; Jin-Lai Gu; Xin-Yuan Jiang; Jie He; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Chen-Wang Lu; Lin-Feng Kuang; Ming-Zhu Liu; Peng-Fei Li; et al. (Fish & Shellfish Immunology, 2026)

Eugenol-mediated molecular regulation: Enabling strong fluorescence and antibacterial activity in bio-based fluorescent polymers - Jiaxin Tao; Guiqiang Li; Xianzhang Wu; Yuan Zhu; Jiawu Xie; Jianshan Chen; Yan Qing (Chemical Engineering Journal, 2026)

Moisture-driven ionogel neuromorphic sensor for apnea detection and event recognition in wearable patches - Xiu-juan Li; Fa Zhang; Ke-yan Li; Xin Li; Zhen-hui Tao; Ke-xin Wang; Zhen-yu Zhang; Guo Fang; Zi-xin Wang; Jia-yi Xie; Long Zhang; Chang-min Yu; et al. (Chemical Engineering Journal, 2026)

Evolutions of tidal flats and tidal creeks under geomorphological and eco-hydrological controls:A case study in the Yellow River Delta, China - Teng Su; Yan Li; Hongyuan Shi; Pengjun Yin; Tao Lu; Qing Wang; Qiuyu Song (CATENA, 2026)

Coupled influence of Western Pacific moisture anomalies and mid-tropospheric humidity on October precipitation in Yunnan Province Southwest China - Wen-Jun Sun; Zhen-Peng Tao; Zi-Yang Zhang; Tian-Qing Lan; Taohui Li; Peng Zi; Jian Zhang; Yao Wu; Ming-Qiang Liang; Chao-Jun Chen; Yuan-Yuan Mu; Jun-Yun Li; et al. (Atmospheric Research, 2026)

The “Last-mile Efforts” of Subseasonal Prediction and Services for Climate Resilience and Sustainability: Review and Outlook - Jing Yang; Mengqian Lu; Anling Liu; Tat Fan Cheng; Yuxian Pan; Miaoni Gao; Lun Dai; Shentong Li; Wen Deng; Xinyao Feng; Shiyu Zhang; Lu Tang; et al. (Advances in Atmospheric Sciences, 2026)
Subseasonal predictions from 2 weeks to 2 months have made significant advancements over the past decade, driven by progress in physical understanding, climate modeling, computational capabilities, and artificial intelligence (AI). These predictions are increasingly in demand due to their potential to provide stakeholders with adequate lead time for effective disaster adaptation, mitigation, and resource management. However, there remain critical gaps in the engagement between prediction providers and service users. Providers often lack insight into the specific needs of users and do not have transferrable strategies to build trust through tailored evaluations and clear confidence levels, which often results in repeatedly devising approaches for each provider–user interaction. Further, users frequently struggle to interpret predictions and are hesitant to make decisions based on these uncertain outcomes. This paper attempts to make “last-mile efforts” by reviewing relevant literature, operational systems, and the most informative communications and engagement strategies with key sectors. It proposes a preliminary framework to standardize the approach for provider–user interaction in the context of subseasonal prediction and services, with potential applicability and extension to seamless prediction systems in the future. Lastly, we underscore future directions for subseasonal predictions, emphasizing the integration of dynamic climate modeling and AI-driven enhancements with large ensemble techniques to improve both reliability and confidence. This review is part of the United Nations Educational Scientific and Cultural Organization (UNESCO) International Decade of Sciences for Sustainable Development (2024–33) and contributes to the Seamless Prediction and Services for Sustainable Natural and Built Environment (SEPRESS) Program (2025–32), an initiative endorsed under this global framework.

Microsphazaphilones H–Y: new azaphilone pigments with HIV latency reversal activity from the marine-derived fungus Microsphaeropsis arundinis P1B - Qing-Ren Lu; Xian-Yuan Yang; Lei Li; Lei-Ming Wu; Lu-Xiang Wan; Yi-Fan Fu; Xian-An Chen; Xin-Xiang Xu; Tao Yuan; Xin Chen; Abrar Ahmed; Nirmal Malik; et al. (Marine Life Science & Technology, 2026)

Structural safety and energy performance of floating offshore photovoltaic systems with stochastic anchor position deviations - Tao Jin; De-Qing Zhang; Jun-Feng Du; Yu Li; Hua-Jun Li (Ocean Engineering, 2026)

Oxygen-mediated electrochemical CO2 mineralization for power generation - Qing Li; Yifan Wu; Yunpeng Wang; Wenchuan Jiang; Cheng Lan; Zhiyu Zhao; Tao Liu; Heping Xie (Journal of Cleaner Production, 2026)

The vinculin-β-catenin axis promotes bone formation and repair: an essential prerequisite for the anti-osteoporotic efficacy of sclerostin-neutralizing antibody - Sixiong Lin; Chu Tao; Yishu Wang; Jianglong Li; YuJia Shi; Qinnan Yan; Yiming Zhong; Huanqing Gao; Tingxuan Wang; Yibo Wang; Qing Yao; Jianmei Huang; et al. (Science China Life Sciences, 2026)

Enhanced Therapeutic Effects of Extracellular Vesicles Targeting MiR-137 Contribute to Functional Recovery by Attenuating Neuronal Injury After Ischemic Stroke - Hui-Xin Zhang; Li-Qing Tao; Yi-Hang Chen; Tian-Yi Jiang; Zhi-Yuan Ye; Wen She; Chang-Ying Chen; Ya-Li Han; Cui Qi; Chong Shen; Jun Gao (Neuroscience Bulletin, 2026)

Preparation of cancer cell membrane-coated Gambogic acid-loaded pH-sensitive liposomes to enhance targeted anti-hepatocellular carcinoma effect - Yi-Feng Zhang; Kun Chen; Yu-Qing Zhu; Lin Liu; Xiang-Tao Kong; Yan Dai; Xiu-Juan Fu; Ya-Ling Li; Ming-Hua Liu; Dan Zhang (Drug Delivery and Translational Research, 2026)

The association between air pollutant exposures and hyperemesis Gravidarum - Yujie Zhou; Qingqing Tao; Quanjun Liu; Qiulin Huang; Mengwei Song; Qing Wang; Qin Li (Journal of Hazardous Materials, 2026)

A wholly coherent wireless energy storage and sensing microsystem toward flexible wearable electronics - Qing You; Chang Gao; Mingjian Pan; Tongkun Wei; Weihe Shen; Xuan Yao; Hanyu Wang; Yuning Li; Xue Li; Jingye Sun; Mingqiang Zhu; Tao Deng (Chemical Engineering Journal, 2026)

Lengthening vegetation carbon turnover time across China’s forests - Rong Ge; Xiaoli Ren; Honglin He; Guirui Yu; Li Zhang; Qian Xu; Mengyu Zhang; Shilong Piao; Kailiang Yu; Mathew Williams; Xiaobo Zhu; Shiyong Yu; et al. (Science Bulletin, 2026)

Genome-wide identification of the laccase gene family in wheat (Triticum aestivum L.) during Fusarium pseudograminearum infection - Li-Yu Chen; Yi Diao; Ju-Hong Ma; Xiang-Xue Zhang; Rui Li; Yan Liu; Hong-Tao Tang; Zhi Wang; Sha Gao; Rui-Huan Xu; Zhen-sheng Kang; De-Jun Han; et al. (Plant Science, 2026)

Integrative analysis of DEHP exposure and prostate cancer: Mechanistic insights and predictive modeling - Wen-Cai Zheng; Wen-Tao Xu; Chao-Ran Chen; Fei Lin; Shao-Hao Chen; Xiao-Dong Li; Xiong-Lin Sun; Qing-Shui Zheng; Yong Wei; Xue-Yi Xue; Zhi-Bin Ke; Ning Xu (Environmental Pollution, 2026)

Traditional cupping-inspired sampling of skin interstitial fluid combined with gold nanobipyramids for multicolor visual detection of miRNAs - Qing Xiong; Chuxiang Hu; Siqi Li; Lisong Pang; Benson K. Kosgei; Xiaoyu Deng; Zhixin Li; Ray P.S. Han; Yingzhou Tao; Shaohua Xu (Chemical Engineering Journal, 2026)

Two new compounds isolated from a sponge-derived fungus Diaporthe sp. ZYX-Z-582 - Jia-Le Chang; Qing-Yun Ma; Li Yang; Qing-Yi Xie; Hai-Tao Li; Jiao-Cen Guo; Hao-Fu Dai; Sha-Sha Liu; You-Xing Zhao (Phytochemistry Letters, 2026)

A comprehensive review of sustainable hazardous waste management: Generation patterns, storage safety, transportation optimization, and treatment technologies - Yanyu Yang; Youcai Zhao; Zihan Zhu; Chuanhua Li; Qing Lu; Tao Zhou (Journal of Hazardous Materials, 2026)

Suspended carrier blended with a high loading of zero-valent iron demonstrates augmentation of anammox bacterial enrichment and bioactivity - Zepeng Wang; Qing Xia; Zhangliang Li; Tao Liu (Journal of Environmental Chemical Engineering, 2026)

Lactic acid modulates empty-cup aroma persistence in Baijiu via molecular interaction mechanisms: a case study of strong-aroma and soy-sauce-aroma Baijiu - Qing-Ru Liu; Shun-Hua Zhang; Xiao-Juan Zhang; Zheng-Juan Zhu; Ru-Yi Li; Song-Tao Wang; Jin-Song Shi; Su-Yi Zhang; Cai-Hong Shen; Guan-Yu Fang; Qing-Qing Liu; Yong-Jun Yuan; et al. (Food Chemistry, 2026)

Structural integrity of the teleost granuloma: a macrophage barrier driven by coordinated activation of junctional, cytoskeletal and extracellular matrix gene networks - Zhengyang Zhou; Linfeng Kuang; Chenwang Lu; Jie He; Zhengqiang Yu; Zhendong Zhong; Quanxin Xiong; Min Qi; Jinlai Gu; Yuanchang Gao; Sheng Lian; Zhengran Jian; et al. (Fish & Shellfish Immunology, 2026)

Virgibacillus aidingensis sp. nov., a bacterium isolated from a hypersaline sediment in Xinjiang Province, North-west China - Li Yang; Hua-Wei Huang; Juan Wang; Cui-Ping Miao; Yi-Qing Li; Xiang-Tao Cen; Li-Xing Zhao; Wen-Yong Zhu; Shu-Kun Tang (Antonie van Leeuwenhoek, 2026)

Single-cell RNA sequencing reveals the immune cell landscape of head kidney in the Perciform fish (Micropterus salmoides) - Zheng-Yang Zhou; Chen-Wang Lu; Zheng-Ran Jian; Shang-Jie Bai; Lin-Feng Kuang; Jin-Lai Gu; Ming-Zhu Liu; Peng-Fei Li; Gao-Xue Wang; Qing Yu; Fei Ling; Jorge Galindo-Villegas; et al. (Aquaculture, 2026)

A carbon sink calculation model for concrete buildings considering time-variant environment - Jia-cheng Xu; Bei Li; Ye Tian; Ruo-yi Zhao; Guo-yi Zhang; Qiang Zeng; Cong-cong Ma; Bo-Tao Huang; Hong-jing Xue; Yun-jian Li; Qing Cai (Environmental Impact Assessment Review, 2026)

Propofol attenuates angiogenesis by activating endoplasmic reticulum stress to suppress TFAP2C-driven VEGFA transcription - Fan Yang; Yi Liu; Hui Li; Xue Shang; Qing Hua; Yun Zhu; Beibei Tao; Zhirong Sun (Apoptosis, 2026)
During anesthesia, significant hemodynamic changes often alter the vascular microenvironment and affecting endothelial cell behavior. Propofol, a commonly used intravenous anesthetic, has been widely studied for its role in tumor angiogenesis through tumor cell–derived VEGF–mediated endothelial interactions. However, its direct effects on endothelial cell–mediated angiogenesis in non-malignant diseases such as diabetic retinopathy, diabetic nephropathy, and coronary heart disease remain unclear. To address this gap, we examined the effects of propofol on VEGFA-mediated angiogenesis in vitro and in vivo. Mechanistically, propofol triggers endoplasmic reticulum stress by promoting phosphorylation of PERK and its downstream effector eIF2α, leading to suppressed translation of TFAP2C—a transcription factor critical for endothelial function. Further analysis revealed that TFAP2C directly binds to the VEGFA promoter to activate its transcription, thereby facilitating VEGFA/VEGFR2-dependent angiogenesis. Together, these findings not only broaden the understanding of propofol’s pharmacological profile, but also identify TFAP2C as a novel transcriptional regulator of VEGFA, offering new perspectives for therapeutic targeting of VEGFA-mediated angiogenesis. Graphical abstract Schematic representation of the mechanism of propofol inhibition of VEGFA/VEGFR2-associated angiogenesis via the PERK/eIF2α/TFAP2C axis.

Metallurgical organic pollutants assisted source apportionment of mobile heavy metals on artisanal non-ferrous metal processing contamination - Li-Rong Liu; Junyao Yan; Lei Xiang; Ting Liu; Ye Xiao; Wen-Shen Liu; Wen-Jun Wu; Ping Li; Miaoyue Zhang; Yuan-Qing Chao; Ye-Tao Tang; Rong-Liang Qiu (Journal of Hazardous Materials, 2025)

Impact of esterification degree of pectic polysaccharides from quinoa microgreen on protective effects against dextran sulfate sodium-induced colitis in mice - Wang Guo; Bo Li; Mao-Qing Wang; Yang Cao; Qin Yuan; Wen Liu; Yi-Chen Hu; Liang Zou; Shengpeng Wang; Ding-Tao Wu (Food Bioscience, 2025)

Sequentially squeezed capacitive pressure sensor based on baguette-inspired porous ionic gel foams - Jian Cheng; Qingzheng Lei; Qibiao Yang; Lie Chen; Deyuan Lou; Qing Tao; Qianliang Li; Zhongsheng Zhai; Dun Liu (Chemical Engineering Journal, 2025)

A flexible bionic bimodal sensor with distinguishing temperature and humidity signals - Xuan Yao; Chang Gao; Mingjian Pan; Tongkun Wei; Weihe Shen; Qing You; Hanyu Wang; Jingru Peng; Danke Chen; Xiaoqiu Tang; Xue Li; Yuning Li; et al. (Chemical Engineering Journal, 2025)

Correction: Multi-Target Inhibitor of ZJQ- 3 F Against AChE/BACE1/GSK3β Targets Improves the Cognitive Impairment of APP/PS1/Tau Triple-Transgenic Mouse Models of Alzheimer’s Disease - Nan Wang; Xin-zhu Li; Xiao-wen Jiang; Xin-yue Ning; Li-jun Zhou; Wen-jie Liu; Qiong Wu; Xin-peng Wang; Yu Xing; Zhen-tong Qi; Zi-hua Xu; Hong-tao Song; et al. (Molecular Neurobiology, 2025)

Integrative single-cell and spatial transcriptome analysis reveals the functions of TREM2high macrophages and infarct border dynamics post-myocardial infarction - Tao Xiong; Yan Chen; Chang Liu; Yaxiong Li; Yayong Zhang; Qing Chang (Molecular and Cellular Biochemistry, 2025)

Harnessing Plant Essential Oils to Combat Acinetobacter baumannii: Research Progress in Antimicrobial Mechanisms and Therapeutic Prospects - Shu-Yun Wei; Yu Sun; Qing Lu; Zhen Liang; Tao Zhu; Yu-Long Li; Ding-Hui Xu; Cai-Ying Li; Feng-Lan Feng; Hong Zeng (Current Microbiology, 2025)

Integrated Geology-Geophysics Exploration of Rare Metal Deposits in the Yidun Island Arc Collisional Orogen - Rong Yang; Yu Peng; Li Qing; Qian-kun Liu; Xue-feng Hao; Han Wu; Jun-bo Fan; Hong-juan Chen; Tao Yang (Applied Geophysics, 2025)

Bidirectionally tuned C(sp3)–H and N–H photo-activation with Wurster-type covalent organic frameworks - Tao-Yuan Yu; Qian Niu; Tao Jiang; Jing-Wen Shi; Qi Li; Qing Huang; Yifa Chen; Shun-Li Li; Ya-Qian Lan (Science Bulletin, 2025)

Discovery of potent ATP citrate lyase inhibitors from Tripterygium wilfordii Hook. f.: a structural and bioactivity analysis - Boquan Qu; Jixia Wang; Yan Li; Tao Hou; Xiaonian Li; Dian Liu; Yang Han; Zhimou Guo; Fengbin Luo; Feifei Huang; Yunhui Zhu; Jiatao Feng; et al. (Phytochemistry, 2025)

Regulating dispersion of OEO Pickering emulsion to construct smart antibacterial nanocellulose packaging films contained microcapsule - Qing Meng; Tao Wang; Siting Li; Hangyu Xie; Honghong Tian; Min Wu; Xueping Song (Food Chemistry, 2025)

Biomimetic co-delivery of Astragaloside IV derivative and Z-Ligustilide for targeted inhibition of EndMT in post-myocardial infarction fibrosis - Pan Liang; Mijia Zhang; Yixuan Wang; Tao Ye; Lihua Wu; Jian Guo; Chun Li; Xin Peng; Wei Ren; Linsen Qing; Pei Luo (Chemical Engineering Journal, 2025)

Dual-mode SERS and colorimetric sensor for lung cancer VOC-biomarker detection using hydrogel patches - Jialin Li; Shaowei Liu; Amil Aligayev; Hao Jiang; Muhammad; Shenhao Wang; Xin Yu; Jin Tao; Jiaqi Wang; Agnieszka Jastrzębska; Qing Huang (Chemical Engineering Journal, 2025)

Four new acylphloroglucinol glucoside derivatives from the leaves of Lysidice rhodostegia - Tian-Yuan Wu; Wei-Xuan Zheng; Xuan Zhou; Kai Zhao; Wei Wu; Li-Qin Zhan; Jin-Tao Fu; Qing Tang; Yu-Bo Zhang; Wen Li; Guo-Cai Wang (Natural Product Research, 2025)

Clonal integration affects the responses of a rhizomatous dune plant to single severe and multiple shallow wind erosion events - Qing Wei; Yu-Kun Hu; Xiao-Lu Shen-Tu; Dan-Dan Li; Tian Li; Hai-Tao Miao; Shou-Li Li (Plant and Soil, 2025)

Recent advances on iron bound phosphorus in wetland sediments: characteristics, influencing factors, interactions with organic matter and emerging contaminants - Yi Tao; Shuai Ma; Manman Cao; Junhong Li; Feng Wang; Ziqi Gao; Qing Xu; Jing Guo; Ke Sun; Fei Wang (Environmental Pollution, 2025)

Crystallization regulation and defect passivation of perovskite films via resonance-structured ionic additive for high-performance solar cells - Guogen Huang; Yuqing Dong; Guanlin Li; Zebing Gao; Chuanlin Gao; Kangbo Sun; Haoxuan Zeng; Haohua Wu; Jinxing He; Xinting Wang; Qing Bai; Tong Shan; et al. (Chemical Engineering Journal, 2025)

The threat of diaphragm closure to thermal runaway during battery charging - Jianqi Zhang; Tao Fan; Zhengnan Liu; Lin Yu; Yuhui Wang; FangZhou Li; Shuai Yuan; Chongye Chang; Kuo Wang; Ziwei Song; Xinming Qian; Qing Wang (Chemical Engineering Journal, 2025)

Linking two types of breccias to sediment-hosted stratiform copper (SSC) and iron oxide-copper-gold (IOCG) deposits in the Kangdian metallogenic belt, SW China - Xue-Qing Yin; Xin-Fu Zhao; Zhi-Kun Su; Hai-Tao Lin; Zhi-Min Zhu; Wen-Lei Song; Martin Yan Hei Li; Kui-Dong Zhao (Mineralium Deposita, 2025)

Solar-driven Janus fabric evaporator: Efficient desalination and selective lithium enrichment - Hong-Bei He; Yue Ma; Qing-Kai Zhu; Ting-Ting Li; Ching-Wen Lou; Jia-Horng Lin; Hai-Tao Ren (Chemical Engineering Journal, 2025)

Multi-Target Inhibitor of ZJQ- 3 F Against AChE/BACE1/GSK3β Targets Improves the Cognitive Impairment of APP/PS1/Tau Triple-Transgenic Mouse Models of Alzheimer’s Disease - Nan Wang; Xin-zhu Li; Xiao-wen Jiang; Xin-yue Ning; Li-jun Zhou; Wen-jie Liu; Qiong Wu; Xin-peng Wang; Yu Xing; Zhen-tong Qi; Zi-hua Xu; Hong-tao Song; et al. (Molecular Neurobiology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Sophormodines A−C, three alkaloids with antiviral activities against the HBV from the seeds of the Tibetan medicine plant Sophora moorcroftiana - Ting-Ting Liu; Meng-Fan Xie; Qing-Qing Yang; Rong-Tao Li; Zhi-Jun Zhang (Phytochemistry, 2025)

Electrospun core–shell structured Ni2GeO4/ZnIn2S4 nanofibers with efficient charge separation efficiency for boosting photocatalytic hydrogen generation - Ziqing Yu; Meng Sun; Li Wang; Jiayu Sun; Tao Yan; Qing Liu; Yu Shao (Fuel, 2025)

Cultured biomass enhances the flavor and nutrition characteristics of biomass/plant hybrid cultured meatballs - Zi-Qing Meng; Chang-Bo Tang; Tian-yi Tao; Wenjuan Song; Chun-Bao Li; Jun Qi; Shi-jie Ding; Guang-Hong Zhou (Food Research International, 2025)

SGLT2i continuously prevents cardiac hypertrophy by reducing ferroptosis via AMPK up-regulation - Bing-bing Zhao; Jiao Wang; Lu-lu Zhang; Chao Li; Hong-hong Xue; Li Zhao; Qing-hua Han; Hong-tao Shi (Molecular and Cellular Biochemistry, 2025)

Fraxetin as a promising natural agent for controlling white spot syndrome virus: Mechanistic insights and application potential - Cheng Chen; Kai-Yuan Lu; Chang-Shuai Liang; Tao Liu; Qing Yu; Peng-Fei Li; Fei Ling; Gao-Xue Wang (Aquaculture, 2025)

Uranium immobilization via sulfur-modified Fe0 nanoparticles: U(VI) trapping kinetics and long-term stability evaluation - Yilong Hua; Xue Meng; Guodong Zhao; Mi Li; Xiaoyan Wu; Xiaowen Zhang; Qing Liu; Tao Cai; Jianping Yang; Wei-xian Zhang; Nan Hu (Journal of Hazardous Materials, 2025)

Identification of key feature variables and prediction of harmful algal blooms in a water diversion lake based on interpretable machine learning - Yundong Wu; Bo Xian; Xiaowei Xiang; Fang Fang; Fuhao Chu; Xingkang Deng; Qing Hu; Xiuqiong Sun; Wei Tang; Shaopan Bao; Genbao Li; Tao Fang (Environmental Research, 2025)

Impact of the actinic radiative effect of scattering aerosols on ozone vertical distribution in the Pearl River Delta, China - Tao Deng; Shanshan Ouyang; Xiaoyang Chen; Guowen He; Xue Zhang; Jeremy Cheuk-Hin Leung; Qing Wang; Zebiao Zhang; Yu Zou; Boru Mai; Li Liu; Xuejiao Deng; et al. (Atmospheric Environment, 2025)

Ginsenoside Rg1 Alleviates Hydrogen Peroxide-Induced Autophagy and Apoptosis in Ovarian Granulosa Cells - Xia Li; Shi-Qi Weng; Qing-Hui Li; Min Ji; Yan Zhou; Qin Xiao; Tao Luo; Zhao-Xia Liu (Cell Biochemistry and Biophysics, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Incorporating atomic-level center into porphyrin-based COF for photocatalytic H2 evolution - Guo-Wei Guan; Su-Tao Zheng; Li-Ping Zhang; Si-Yu Hou; Xiang-Yu Liu; Qing-Yuan Yang (Chemical Engineering Journal, 2025)

Key role of recycled terrigenous sediments in generating continental arc magmatism in the West Qinling orogen, China - Li-Tao Ma; Li-Qun Dai; Hao Liang; Ye-Dan Hu; Qing-Cheng Yang; Zi-Fu Zhao; Guo-Chao Sun (Chemical Geology, 2025)

Isolation and identification of a novel bisacodyl analogue, bisacodyl dicycloproyl carboxylate, as a potential illegal additive in a dried plum product advertised for weight loss - Xian-Xian Li; Feng Jiang; Hong Yu; Xiao-Jing Huang; Jing-Xian Zhang; Jin-Tao Xia; Ying-ying Ran; Fan Huang; Jian Sun; Qing Hu (Food Additives & Contaminants: Part A, 2025)

Cereal-legume intercropping stimulates straw decomposition and promotes soil organic carbon stability - Wei Wang; Meng-Ying Li; Qing-Hui Wen; Yue Ma; Zhi-Ming Zhang; Muhammad Maqsood Ur Rehman; Fei Mo; Hong-Yan Tao; Bao-Luo Ma; Joann K. Whalen; You-Cai Xiong (Science China Life Sciences, 2025)

A new sesquiterpene from endophytic fungus Colletotrichum sp. B-89 - Ke-tao Zhang; Bing Zhang; Zhi-pu Huang; Yu-xiao Xu; Xiao-rong Xu; Si-heng Li; Qing Zhao; Xiao-mei Zhang (Natural Product Research, 2025)

Preconception maternal hyperoxia exposure causes cardiac insufficiency through induction of mitochondrial toxicity in mice offspring - Dan Chen; Zhi-xuan Xing; Sheng-peng Li; Tao Lu; Jia-xin Wang; Ya-xian Wu; Qing-feng Pang (Reproductive Toxicology, 2025)

The combination of metagenomics and metabolomics reveals the effect of nitrogen fertilizer application driving the remobilization of immobilization remediation cadmium and rhizosphere microbial succession in rice - Huan-Zhan Zhou; Bu-Qing Wang; Yong-Hong Ma; Yu-Ying Sun; Huan-Lin Zhou; Zhen Song; Yuan Zhao; Wei Chen; Jie Min; Jing-Wen Li; Tao He (Journal of Hazardous Materials, 2025)

Enhanced ammonia synthesis using surface microdischarge with metal-loaded nickel foam electrodes - Yue Feng; Yuzhuo Cai; Yaolin Wang; Tianyu Li; Santu Luo; Wenpeng Liang; Sutao Zheng; Tao Xie; Qing-Yuan Yang; Xue Yong; Renwu Zhou; Dingxin Liu; et al. (Chemical Engineering Journal, 2025)

Genomic, transcriptomic, and metabolomic analyses reveal convergent evolution of oxime biosynthesis in Darwin’s orchid - Kai Jiang; Birger Lindberg Møller; Shaofan Luo; Yu Yang; David R. Nelson; Elizabeth Heather Jakobsen Neilson; Joachim Møller Christensen; Kai Hua; Chao Hu; Xinhua Zeng; Mohammed Saddik Motawie; Tao Wan; et al. (Molecular Plant, 2025)

A Gln alteration influences leaf morphogenesis by mediating gibberellin levels in tobacco - Qi-Li Mi; Hong-Tao Lv; Fei-Fei Huang; Li Xu; Zi-Ying Huang; Wen-Wu Yang; Mei-Yun Zou; Hai-Tao Huang; Wan-Li Zeng; Jia-Yin Zhao; Qing-Xian Chen; Yong-En Si-Tu; et al. (Journal of Plant Physiology, 2025)

The association between anthropogenic heat and parent-report symptoms of childhood attention deficit hyperactivity disorder in China: A novel perspective reflecting climate change - Tao Yu; Yue Wen; Pei-Pei Dong; Ming-Kun Sun; Samantha E. Qian; Mario Schootman; Michael G. Vaughn; Shu-Li Xu; He-Hai Huang; Feng-Wen Shan; Shi-Fu Zhu; Jing-Yao Wang; et al. (International Journal of Hygiene and Environmental Health, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Overcoming the conventional thermodynamic limit of water electrolysis to boost renewable energy storage - Hui Sun; Wen-Tao Bi; Qian He; Li Zhu; Yu-Qing Dong; Fang Li; Zhen-Guo Guo; Jun Ding; Jian-Bo He (Chemical Engineering Journal, 2025)

Development and evaluation of a sulfate precipitation method for separating key flocculated-species from titanium-based flocculant - Mingqian Hou; Wenhui Guo; Hao Xu; Chunyi Sun; Xu Zhao; Xiaomei Gao; Xuguang Li; Tao Yan; Shou-Qing Ni; Liangguo Yan; Yanxia Zhao (Water Research, 2025)

Investigation of Cyclospora spp. in farmed fur animals based on PCR-RFLP - Nian-Yu Xue; Hai-Tao Wang; Qing-Yu Hou; Ya Qin; Xue-Min Li; Jing Jiang; Li-Hua Yang; Xing Yang; Yan Tang (Veterinary Parasitology, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

Effects of Chinese Herbal Medicines on Growth Performance, Antioxidant Capacity, and Liver and Intestinal Health of Hybrid Snakehead (Channa maculata ♀ × Channa argus ♂) - Jiamin Kang; Shuzhan Fei; Junhao Zhang; Haiyang Liu; Qing Luo; Mi Ou; Langjun Cui; Tao Li; Jian Zhao (Fishes, 2025)
Chinese herbal medicines have become a new green feed additive in the aquaculture industry. The aim of this study is to investigate the effects of traditional Chinese herbal medicines (Isatidis radix, Forsythia suspensa, and Schisandra chinensis) on the growth performance, antioxidant capacity, and intestinal microbiota of hybrid snakehead (Channa maculata ♀ × Channa argus ♂). A total of 600 fish (mean weight: 15.85 ± 0.15 g) were randomly assigned to five groups, including the control group (CG), I. radix extract group (IRE), F. suspensa extract group (FSE), S. chinensis extract group (SCE), and the Chinese herbal medicine mixture group (CHMM; a mixture of extracts of I. radix, F. suspensa, and S. chinensis at the ratio of 1:1:1) for 6 weeks. The results show that the IRE-supplemented diet improved the survival rate (SR), feed efficiency ratio (FE), and condition factor (CF) compared to others. Compared to the control group, the activity of superoxide dismutase (SOD) in plasma and intestine was significantly increased in the FSE and CHMM groups, whereas the content of malondialdehyde (MDA) in plasma and liver was significantly reduced in the SCE group. A 16s rRNA analysis indicates that dietary supplementation with FSE significantly promoted the proliferation of Fusobacteriota, while IRE supplementation increased the alpha diversity of intestinal bacteria. In conclusion, the addition of I. radix to the diet of hybrid snakehead improves growth, antioxidant capacity, and liver and intestine health, and modulates the intestinal microbiota of snakehead positively.

Study on the Role and Pathological and Immune Responses of Silver Nanoparticles Against Two Aeromonas salmonicida subsp. salmonicida Strains at Different Virulence Levels in Rainbow Trout (Oncorhynchus mykiss) - Yunqiang Guo; Chaoli Zheng; Yingfei Wang; Yongji Dang; Ruiyuan Li; Ye Tao; Yucheng Yang; Xiaofeng Sun; Zekun Song; Pengcheng Sun; Qian Zhang; Dandan Qian; et al. (Fishes, 2025)
Aeromonas species are among the main pathogens causing rainbow trout infections. Silver nanoparticles (AgNPs) have a broad spectrum of antimicrobial properties and are usually produced by various green-synthesis methods. However, the application of commercialized AgNPs has not fully been clarified. Thus, the objective of this study was to evaluate the antibacterial activities of commercialized AgNPs (range of sizes 10–12 nm) on two contrasting A. salmonicida strains (I-1 and I-4), isolated from rainbow trout; the antibacterial mechanism, histopathological alterations and the expression of immune-related genes were investigated. In vitro, the minimal inhibitory concentration (MIC) was 10 µg/mL for I-1, and lowered to 9.5 µg/mL for I-4, respectively. AgNPs were shown to disrupt both the cell wall and membrane of I-1 and I-4, resulting in cell lysis and degradation. In vivo, rainbow trout challenged by immersed or intraperitoneally injected infection, the 10 µg/mL AgNP-treated groups, both showed delayed deaths and lower mortalities compared to the control groups, without any clinical signs and pathological changes. Especially for the virulent I-4, the enhanced expressions of immune-related genes TNF-α, IL-1β, IL-10 and IL-11 were significantly reduced in the AgNP-treated group, indicating a lesser inflammation due to the application of AgNPs. This study would lay theoretical foundation for the wide application of silver nanoparticles in fish diseases.

Dietary lecithin attenuates adverse effects of high fat diet on growth performance, lipid metabolism, endoplasmic reticulum stress and antioxidant capacity in the intestine of largemouth bass (Micropterus salmoides) - Hua Zheng; Biao Wang; Qing-Lin Li; Tao Zhao; Peng-Cheng Xu; Yu-Feng Song; Zhi Luo (Aquaculture, 2025)

Comparative analysis of carotenoids, fatty acids, minerals, tastes, and odor in the skin of wild versus farmed large yellow croaker: Superior nutritional benefits with elevated heavy metal risks - Jia-Lang Zheng; Tao Zhu; Wang-Yang Jin; Qing-Hao Zhan; Fa-Guo Wan; Yong-Long Chen; Tian-Hong Chen; Shun Chen; Qing-Ling Zhu; Shuang Chen; Wei-Ye Li; Yi-Fan Liu; et al. (Aquaculture, 2025)

Investigating the matrix effect of high/low methoxyl pectins on typical aroma of apple juice using HS-SPME-GC–MS and NMR analysis - Wan Qing Li; Hui Liu; Yu Rong Guo; Xiao Yu Wang; Peng Tao Zhao (Food Chemistry, 2025)

MFNT catalysts enhanced by the radio-frequency cold plasma preparation with wide temperature NH3-SCR activity: A combined experimental and DFT study - Junqiang Xu; Maolin Xie; Tao Zheng; Qing Liu; Hong Shen; Yanlan Li; Kuang-Hsu Wu; Jiayun Zhang; Fang Guo; Qiang Zhang; Minghua Duan (Chemical Engineering Journal, 2025)

Knockdown of DJ-1 Exacerbates Neuron Apoptosis Induced by TgCtwh3 through the NF-κB Pathway - Di Yang; Minmin Wu; Nian Zou; Yiru Tang; Qing Tao; Lei Liu; Mengmeng Jin; Li Yu; Jian Du; Qingli Luo; Jilong Shen; Deyong Chu; et al. (Molecular Neurobiology, 2025)
Mutations or loss of function of DJ-1 and Toxoplasma gondii ( T. gondii ) infection has been linked to neurodegenerative diseases, which are often caused by oxidative stress. However, the relationship between DJ-1 and T. gondii infection is not yet fully understood. Therefore, this study aimed to investigate the expression of DJ-1 in the hippocampus tissue of mice or in HT22 infected with T. gondii Chinese 1 genotype Wh3 strain (TgCtwh3) and the effect of DJ-1 knockdown on neuronal apoptosis induced by TgCtwh3 tachyzoite, as well as the underlying mechanism at the cellular and molecular level. Firstly, we detected DJ-1 protein expression and cell apoptosis in the hippocampal tissue of mice infected by TgCtwh3. Then, we examined DJ-1 expression and apoptosis in HT22 challenged with TgCtwh3. Finally, we evaluated the apoptosis in HT22 with DJ-1 knockdown which was infected with TgCtwh3 and assayed the expression of NF-κBp65 and p -NF-κBp65. Our results showed that DJ-1 expression was reduced and neurons underwent apoptosis in the hippocampus of mice infected with TgCtwh3 tachyzoites. Additionally, the knockdown of DJ-1 followed by infection with TgCtwh3 tachyzoites led to increased apoptosis in HT22 cells through the NF-κB signaling pathway. Therefore, this study suggests that DJ-1 is an important target for preventing apoptosis caused by T. gondii TgCtwh3.

The beneficial potential of protein hydrolysates as prebiotic for probiotics and its biological activity: a review - Ping-Ping Gao; Han-Qing Liu; Zhi-Wei Ye; Qian-Wang Zheng; Yuan Zou; Tao Wei; Li-Qiong Guo; Jun-Fang Lin (Critical Reviews in Food Science and Nutrition, 2024)

Effect of the LIF gene on the cell cycle and apoptosis of ovarian granulosa cells in white Muscovy ducks - Qing-hua Tao; Ning-ning Sun; Meng-shi Wang; Wan-xin Zhao; Wei Liu; Xu Zhang; Ang Li (Theriogenology, 2024)

Design and green synthesis of asymmetric 3,4,5-trimethoxyphenyl-inspired 1,5-diaryl-1,4-pentadien-3-ones as potent anti-gastric cancer agents through ROS and JNK-triggered apoptosis - Jianzhang Wu; Song Yao; Danjie Wang; Mengke Han; Yingwen Liu; Shuo Ren; Liping Chen; Min Zhu; Qian Li; Tao Wu; Yujia Li; Jiabing Wang; et al. (Sustainable Chemistry and Pharmacy, 2024)

Investigating how oxygen levels and particle size impact the thermodynamics of low temperature coal oxidation: A case study using weakly caking coal - Li-Feng Ren; Fan Tao; Teng-Fei Weng; Qing-Wei Li; Xin Yu; Xiao-Wei Zhai; Teng Ma (Fuel, 2024)

Sturgeon (Acipenser schrenckii) spinal cord peptides: Antioxidative and acetylcholinesterase inhibitory efficacy and mechanisms - Xiaoyan Zu; Qing Zhao; Wenbo Liu; Lu Guo; Tao Liao; Jun Cai; Hailan Li (Food Chemistry, 2024)

Towards wearable multifunctional cellulose nanofiber/silver nanowire/graphene oxide film: Electromagnetic protection, antibacterial, and motion monitoring - Zheng Wang; Shi-Bo Li; Xiao Yang; Hao Wang; Li-Jing Xie; Ze-Chao Tao; Qing-Qiang Kong; Shou-Chun Zhang; Hui Jia; Dong Jiang; Cheng-Meng Chen (Chemical Engineering Journal, 2024)

MEIKIN expression and its C-terminal phosphorylation by PLK1 is closely related the metaphase–anaphase transition by affecting cyclin B1 and Securin stabilization in meiotic oocyte - Li-Hua Fan; Shu-Tao Qi; Zhen-Bo Wang; Ying-Chun Ouyang; Wen-Long Lei; Yue Wang; Ang Li; Feng Wang; Jian Li; Li Li; Yuan-Yuan Li; Yi Hou; et al. (Histochemistry and Cell Biology, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

The role of Nocardia seriolae-induced autophagy in the development of chronic inflammation in the liver and the formation of granulomas in largemouth bass (Micropterus salmoides) - Shang-Jie Bai; Zheng-Ran Jian; Sheng-Yu He; Lin-Feng Kuang; Zheng-Yang Zhou; Chen-Wang Lu; Zhen-Dong Zhong; Jie He; Quan-Xin Xiong; Shuang-Yan Xiao; Peng-Fei Li; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Flavopiridol inhibits oocyte maturation, reduces oocyte quality and blocks cumulus cell function - Xiao-Zhen Li; Li-Tao Yi; Qing-Yuan Sun; Chang-Long Xu; Shen Yin (Toxicology Letters, 2024)

A molecular mechanism underlies grass carp (Ctenopharyngodon idella) TARBP2 regulating PKR-mediated cell apoptosis - Miao-miao Li; Chang-bai Tao; Mei-feng Li; Chu-xin Wu; Ting-ting Yu; Zhi-qing Feng; Qing-Zhang; Ze-yin Jiang; Hui-ling Mao; Shang-hong Wang; Xiao-wen Xu; Cheng-yu Hu (Fish & Shellfish Immunology, 2024)

Roles and fates of antibiotics in anaerobic digestion of waste activated sludge: Insights to pro- and re-duction of antibiotic resistance genes - Qing-Bin Meng; Zhang-Wei He; Wenjing Yang; Wen-Tao Li; Cong-Cong Tang; Ai-Juan Zhou; Yong-Xiang Ren; Wenzong Liu; Zhihua Li; Aijie Wang (Chemical Engineering Journal, 2024)

Dual-continuous microneedle patch integrating transdermal delivery of pH-sensitive licorzinc MOFs and Zn2+ hydrogel sensors for treating alopecia areata - Hang Ruan; Yuwen Zhong; Huining Ding; Zehui He; Jiaqi Li; Meng Long; Zhi Wang; Qing Xia; Teng Guo; Chunyun Zhu; Tao Yang; Nianping Feng; et al. (Chemical Engineering Journal, 2024)

Acinetobacter corruptisaponis sp. nov., Isolated from a Spoiled Bath Lotion - Ying-Si Wang; Gang Zhou; Hong-Bing Tao; Lei Gao; Bao-Zhu Fang; Xiu-Jiang Yang; Hong Peng; Xia Wen; Xiao-Mo Huang; Jie Wang; Wen-Jun Li; Qing-Shan Shi; et al. (Current Microbiology, 2024)

The response of surface sedimental diatoms to the environment and its potential significance in the Taiwan Strait, western Pacific - Min Chen; Xuan Liu; Shuqin Tao; Aijun Wang; Yanting Lin; Zhaohe Luo; Ya Xu; Jiayu Li; Qing Huang (Acta Oceanologica Sinica, 2024)

Comparative study on the quality of wild and ecologically farmed large yellow croaker through on-site synchronous sampling from the Nanji Archipelago in the East China Sea - Jia-Lang Zheng; Yong-Long Chen; Fa-Guo Wan; Qing-Hao Zhan; Tian-Hong Chen; Shun Chen; Qing-Ling Zhu; Li-Hua Jiang; Wei-Ye Li; Wen-Tao Ye; Yi-Fan Liu; Wei-Hua Song; et al. (Aquaculture, 2024)

Discovery and engineering of ChCas12b for precise genome editing - Jingjing Wei; Jingtong Liu; Yuwen Tian; Ziwen Wang; Linghui Hou; Yuan Yang; Chen Tao; Miaomiao Li; Bao-Qing Gao; Huanyu Zhou; Xixi Zheng; Junnan Tang; et al. (Science Bulletin, 2024)

A Janus evaporator based on Donnan effect for efficient solar thermal desalination - Hai-Tao Ren; Hong-Bei He; Qing-Kai Zhu; Ting-Ting Li; Ching-Wen Lou; Jia-Horng Lin (Desalination, 2024)

Effects of cadmium on the intestinal health of the snail Bradybaena ravida Benson - Yan-Mei Da; Shun-Shun Li; Yan-Qi Li; Le-Yu Deng; Ming-Jun Li; Tao Huang; Qing-Ye Sun; Jazbia Shirin; Guo-Wei Zhou (Ecotoxicology, 2024)

Dissolved oxygen fluctuation alters dissolved organic carbon stability and can accumulate resistant fraction - Yu-Qing Li; Fu-Tao Fang; Cong Zeng; Zhuo-Yi Zhu (Marine Chemistry, 2024)

Nucleobase-modulated copper nanomaterials with laccase-like activity for high-performance degradation and detection of phenolic pollutants - Tao Yang; Yuanyuan Li; Gonghao Liu; Jiajun Tong; Peng Zhang; Bo Feng; Ke Tian; Xiaofeng Liu; Taiping Qing (Journal of Hazardous Materials, 2024)

Molecular insights into the catalytic mechanism of a phthalate ester hydrolase - Ning Wang; Nan Zhang; Mei-Ling Sun; Yan Sun; Qing-Yu Dong; Yu Wang; Zeng-Tian Gu; Hai-Tao Ding; Qi-Long Qin; Yong Jiang; Xiu-Lan Chen; Yu-Zhong Zhang; et al. (Journal of Hazardous Materials, 2024)

Multi-omics insights into the function and evolution of sodium benzoate biodegradation pathway in Benzoatithermus flavus gen. nov., sp. nov. from hot spring - Chao-Jian Hu; Yi-Qing Lv; Wen-Dong Xian; Jian-Yu Jiao; Zheng-Han Lian; Sha Tan; Meng-Meng Li; Zhen-Hao Luo; Ze-Tao Liu; Ai-Ping Lv; Lan Liu; Mukhtiar Ali; et al. (Journal of Hazardous Materials, 2024)

Simultaneous enhancement of ductility and sustainability of high-strength Strain-Hardening Cementitious Composites (SHCC) using recycled fine aggregates - Qing-Hua Li; Shu-Yue Zhao; Bo-Tao Huang; Ling-Yu Xu; Shi-Lang Xu (Journal of Cleaner Production, 2024)

Bond behavior between steel bar and strain-hardening fiber-reinforced cementitious composites under fatigue loading - Qing-Hua Li; Ai-Min Luo; Bo-Tao Huang; Guo-Zhong Wang; Shi-Lang Xu (Engineering Structures, 2024)

Spray of water-in-oil emulsified heavy oil with high water content - Ruo-Fan Shi; Yu-Feng Xi; Li-Tao Wang; Hong-Jun Lu; Xiao Zhang; Xin-Yue Zhang; Zi-Bin Huang; Pei-Qing Yuan (Chemical Engineering Journal, 2024)

Impact of aerosol actinic radiative effect on ozone during haze pollution in the Pearl River Delta region - Tao Deng; Shanshan Ouyang; Guowen He; Xue Zhang; Jeremy Cheuk-Hin Leung; Xiaoyang Chen; Qing Wang; Zebiao Zhang; Yu Zou; Boru Mai; Li Liu; Xuejiao Deng (Atmospheric Environment, 2024)

Phytochrome B interacts with LIGULELESS1 to control plant architecture and density tolerance in maize - Qingbiao Shi; Ying Xia; Qibin Wang; Kaiwen Lv; Hengjia Yang; Lianzhe Cui; Yue Sun; Xiaofei Wang; Qing Tao; Xiehai Song; Di Xu; Wenchang Xu; et al. (Molecular Plant, 2024)

Microbes and nutrient shift in a Closed Aquatic Ecosystem (CAES) during four weeks of operation - Peifan Gu; Xianyuan Zhang; Anji Chen; Qing Tian; Jing Zhang; Tao Li; Xiaoyan Li; Gaohong Wang (Life Sciences in Space Research, 2024)

Potential of Cordyceps militaris protein hydrolysates as prebiotic and thermo-protectants of Lactobacillus fermentum J26 - Ping-Ping Gao; Han-Qing Liu; Qian-Wang Zheng; Yuan Zou; Zhi-Wei Ye; Tao Wei; Li-Qiong Guo; Jun-Fang Lin (Food Bioscience, 2024)

Catechol compounds as dual-targeting agents for fish protection against Ichthyophthirius multifiliis infections - Shen-Ye Qu; Yi-Hang Liu; Jie-Tao Liu; Peng-Fei Li; Tian-Qiang Liu; Gao-Xue Wang; Qing Yu; Fei Ling (Fish & Shellfish Immunology, 2024)

Immobilization of Nickel- and Cobalt-Based Complexes in NH2-UiO-66 for Efficient CO2 Photoreduction - Yu Jiang; Si-Chao Liu; Li-Ping Zhang; Guo-Wei Guan; Yi-Tao Li; Shuang Ni; Run-Yuan Jiang; Su-Tao Zheng; Hao-Ran Liu; Hao-Ling Lan; Qing-Yuan Yang (Chemical Engineering Journal, 2024)

Antibacterial and anti-inflammatory synergistic effects of double-layer hydrogel promoting bacterial wound healing - Chunyang Li; Jin-Tao Wang; Kuili Liu; Hongwei Ding; Qing-Feng Li; Gaofeng Liang; Lin Jin; Deyan He (Chemical Engineering Journal, 2024)

Simultaneously reducing the intensity and increasing the frequency of sand movements promotes the performance of Artemisia ordosica seedlings in dune environments - Li-Chen Tang; Xiao-Lu Shen-Tu; Qing Wei; Hai-Tao Miao; Shou-Li Li (Plant and Soil, 2024)

Experimental evidence that nitrogen-fixing cyanobacterium Trichodesmium spp. supplies new nitrogen source to marine phytoplankton - Shuang-Qing Li; Yan Xiao; Hai-Long Huang; Zhen Luo; Tao-Ran Sun; Hua-Yang Gao; Xin-Wei Wang; Hai-Bo Jiang (Frontiers in Marine Science, 2024)
In oligotrophic oceans, primary productivity is widely limited by nitrogen bioavailability. The broadly distributed and abundant nitrogen-fixing cyanobacterium Trichodesmium plays an important role in the oceanic nitrogen and carbon cycles by providing a “new” source of nitrogen to many non-diazotrophic microbes, thereby driving new primary production in the ocean. However, the underlying process and mechanism of nitrogen supply from Trichodesmium to other phytoplankton remain unclear. Here, our results demonstrated that the fixed nitrogen released by Trichodesmium could sustain the growth of a non-nitrogen-fixing cyanobacterium Synechococcus sp. PCC 7002, including a mutant strain (Mut- ureA ) that cannot use urea. However, the growth rate of Mut- ureA was approximately 20% lower than that of the wild strain when Trichodesmium filtrate was used for nitrogen supply. This result was consistent with the composition of the Trichodesmium exudate, in which urea comprised more than 20% of the total fixed nitrogen that was released. It is evident from the experiments that a fraction of the Trichodesmium -derived nitrogen was not available to Mut- ureA . Our results suggested that Trichodesmium produces dissolved organic nitrogen, especially a certain amount of urea as a “new” nitrogen source, benefiting in particular populations of surrounding phytoplankton species.

Mitochondrial damage and activation of NLRP3 induced by Yersinia ruckeri infection play an important role in the occurrence of diffuse acute inflammation of channel catfish (Ictalurus punctatus) - Chen-Wang Lu; Jie He; Quan-Xin Xiong; Zhen-Dong Zhong; Bin Yang; Sheng Lian; Meng-Meng Wang; Shang-Jie Bai; Lin-Feng Kuang; Zheng-Yang Zhou; Zheng-Ran Jian; Yuan-Chang Gao; et al. (Aquaculture, 2024)

Numerical simulation of wedges slamming non-Newtonian fluids based on SPH method - Jie Cui; Qing Yao; Xin Chen; Ming-Yuan Li; De-Tao Xu (Ocean Engineering, 2024)

Syn- and post-collisional mafic igneous rocks from the East Kunlun Orogenic Belt: Implications for recycling of subducting continental crust during the Silurian-Devonian - Li-Tao Ma; Guo-Chao Sun; Li-Qun Dai; Zi-Fu Zhao; Ye-Dan Hu; Qing-Cheng Yang; Lei Qin; Bing Gong (Lithos, 2024)

Associations between exposure to phthalates and liver function among women undergoing assisted reproductive technology - Yi Wang; Li Yin; Yao-Yao Du; Hong-Mei Liao; Juan Li; Wen Yao; Xiao-Qiong Yuan; Qing-Chun Guo; Tao-Ran Deng; Na Guo; Min Zhang; Qiang Zeng; et al. (Environmental Toxicology and Pharmacology, 2024)

Nanoconfinement-induced high activity of ZIF-8 derived atomic Zn-N-C materials for fenton-like reactions - Lipeng Wu; Xiaomin Wang; Pengwei Zhao; Yongsheng Ji; Bin Li; Yongsheng Xu; Tao Liao; Qing Xia; Yang Li; Xiaobin Fan; Wenchao Peng (Chemical Engineering Journal, 2024)

Primary Cutaneous Mucormycosis Caused by Mucor irregularis in a Chinese Man - Zhihua Li; Qing Jiang; Xiaohua Tao; Zhenhua Zhang; Luhuai Shi; Lifang Cheng; Pingxiu He; Xinyi Fan; Rui Xu; Yunpeng Luo; Yangmin Gao (Mycopathologia, 2024)

Clinical Characteristics and Pathogen Spectrum of Male Genital Fungal Infections in Nanchang Area, South China - Yun Jin; Yangmin Gao; Yunpeng Luo; XiaoHua Tao; Qing Jiang; Xinyi Fan; Rui Xu; Hua Qian; Xiaoguang Li; Zhijun Zhou (Mycopathologia, 2024)
The cutaneous fungal infections in male genitalia are relatively rare, and often present with various atypical clinical symptoms. It was mainly reported in a small number of case reports, while data with large number of patients were rarely reported. In this study, we reported 79 male patients with cutaneous fungal infections on scrotum or penis. The fungal infections were confirmed by microscopic examination directly and fungus culture. Clinical characteristics and predisposing factors were also collected. Of these 79 patients, 72 has lesions on scrotum, 5 on penis and 2 on both scrotum and penis. Trichophyton (T.) rubrum is the most common pathogen, found in 50 (67.6%) patients, which presented diverse clinical manifestation such as majorly erythematous, dry diffused scaly lesions without a clear border, slightly powdery and scutular scalings. Candida (C.) albicans is the secondly common pathogen, found in 21 (28.4%) patients, which also presented diverse lesions such as erythematous with dry whitish scaly lesions and erythematous erosion. The predisposing factors mainly included concomitant fungal infections on sites other than genitalia, especially inguinal region (tinea cruris), application of corticosteroid and high moisture. In conclusion, cutaneous fungal infections in male genitalia could be caused by different fungi, showed atypical or mild clinical appearances in most cases and might be a fungus reservoir, emphasizing the necessity to timely perform the fungi examinations and corresponding therapy.

High levels of cadmium altered soil archaeal activity, assembly, and co-occurrence network in volcanic areas - Zihua Zhang; Daolong Xu; Tao Huang; Qing Zhang; Yingyue Li; Jing Zhou; Ruifan Zou; Xiaoyu Li; Jin Chen (Science of The Total Environment, 2024)

Sublethal effects of chlorantraniliprole on immunity in Spodoptera frugiperda (Smith) (Lepidoptera: Noctuidae): Promote encapsulation by upregulating a heat shock protein 70 family gene SfHSP68.1 - Wenqi Xie; Xiaoyue Deng; Wencai Tao; Zhihui Zhang; Huilai Zhang; Qing Li; Chunxian Jiang (Pesticide Biochemistry and Physiology, 2024)

Characteristics of industrialized hydrothermal cracking solid organic fertilizer and its effects on fresh corn growth - Jue Wang; Rui Xia; Chunfang Xu; Xiaoxiao Yang; Yanming Li; Qinghai Li; Tao Zhang; Qing Chen; Hui Zhou; Yanguo Zhang (Waste Management, 2024)

Effects of interactions between arbuscular mycorrhizal fungi and bacteria on the growth of Lotus corniculatus L.: From the perspective of regulating rhizosphere fungal community - Qing ZHANG; Jin CHEN; Yingyue LI; Tao HUANG; Kailing XIE; Jing ZHOU; Xiaoyu LI (Pedosphere, 2024)

Macro–micro investigation on stabilization sludge as subgrade filler by the ternary blending of steel slag and fly ash and calcium carbide residue - Jian–feng Zhu; Zheng–qing Wang; Yan–li Tao; Lu–ying Ju; Hao Yang (Journal of Cleaner Production, 2024)

Constructing of Fe-Cu bimetallic MOFs derived electro-Fenton cathode for efficient norfloxacin removal - Yixin Du; Zhenpeng Li; Rui Feng; Qing Liu; Yanming Yang; Meng Sun; Yanxia Zhao; Tao Yan; Liangguo Yan (Journal of Environmental Chemical Engineering, 2024)

A comprehensive review on the characteristics and kinetics of freshwater separation by hydrate-based method: Current progress, challenges and perspectives - Xuemin Zhang; Jiajing He; Tao Shan; Qingqing Liu; Qing Yuan; Jinping Li; Qingbai Wu; Peng Zhang (Desalination, 2024)

Triblock polymer PDMAEMA-co-PNIPAM-co-PMPC to deliver siKRAS for gene therapy in pancreatic cancer - Lidong Cao; Mengmeng Dong; Kai Jiang; Qing Zhu; Feng Li; Zunqiang Xiao; Hao Tang; Ran Tao (Chemical Engineering Journal, 2024)

Inflammatory cell death PANoptosis is induced by the anti-cancer curaxin CBL0137 via eliciting the assembly of ZBP1-associated PANoptosome - Ya-Ping Li; Zhi-Ya Zhou; Liang Yan; Yi-Ping You; Hua-Yu Ke; Tao Yuan; Hai-Yan Yang; Rong Xu; Li-Hui Xu; Dong-Yun Ouyang; Qing-Bing Zha; Xian-Hui He (Inflammation Research, 2024)

Will the Globe Encounter the Warmest Winter after the Hottest Summer in 2023? - Fei Zheng; Shuai Hu; Jiehua Ma; Lin Wang; Kexin Li; Bo Wu; Qing Bao; Jingbei Peng; Chaofan Li; Haifeng Zong; Yao Yao; Baoqiang Tian; et al. (Advances in Atmospheric Sciences, 2024)

Subnano-Fe (Co, Ni) clusters anchored on halloysite nanotubes: an efficient Fenton-like catalyst for the degradation of tetracycline - Qing Sun; Jiale Yu; Youpu Zhao; Hanhu Liu; Chunsheng Li; Jiajun Tao; Jian Zhang; Jiawei Sheng (Environmental Science and Pollution Research, 2024)

Chemical constituents from the aerial parts of Rubia cordifolia L. with their NO inhibitory activity - Hong Zhang; Wen-Tao Fang; Yan Li; Qing-Hua Kong; Cheng-Wu Fang; Han Luo; Shou-Jin Liu (Natural Product Research, 2024)

Anthropogenic activities enhance mercury methylation in sediments of a multifunctional lake: Evidence from dissolved organic matter and mercury-methylating microorganisms - Juan Wang; Qing Xie; Yuping Xiang; Jinping Xue; Tao Jiang; Cheng Zhang; Jiajia Li; Yongmin Wang; Dingyong Wang (Journal of Hazardous Materials, 2024)

Effects of biochar pyrolysis temperature on uranium immobilization in soil remediation: Revealed by 16S rDNA and metabolomic analyses - Huachuan Feng; Yilin Wang; Nan Li; Zishu Qian; Tao Chen; Xiaoming Chen; Qing Wang; Wenkun Zhu (Journal of Hazardous Materials, 2024)

Impact of deoxynivalenol on rumen function, production, and health of dairy cows: Insights from metabolomics and microbiota analysis - Jia-nan Dong; Zhi-kun Zhao; Zhan-qing Wang; Song-ze Li; Yong-peng Zhang; Zhe Sun; Gui-xin Qin; Xue-feng Zhang; Wei Zhao; Natnael Demelash Aschalew; Tao Wang; Yu-guo Zhen (Journal of Hazardous Materials, 2024)

Influence on the volatilization of ethyl esters: Nonnegligible role of long-chain fatty acids on Baijiu flavor via intermolecular interaction - Qing-Ru Liu; Xian-Li Lin; Zhen-Ming Lu; Li-Juan Chai; Song-Tao Wang; Jin-Song Shi; Su-Yi Zhang; Cai-Hong Shen; Xiao-Juan Zhang; Zheng-Hong Xu (Food Chemistry, 2024)

Highly efficient separation of pyrrolidine and tetrahydrofuran by using solid crystal powder of Cucurbit[6]uril - Yu Zhang; Zhu Tao; Qing Li (Chemical Engineering Journal, 2024)

Virgin coconut oil: A comprehensive review of antioxidant activity and mechanisms contributed by phenolic compounds - Yu-Qing Zeng; Jin-Tao He; Bo-Yong Hu; Wen Li; Jing Deng; Qin-Lu Lin; Yong Fang (Critical Reviews in Food Science and Nutrition, 2024)

Nocardia seriolae mediates granulomatous chronic inflammation of spleen in Micropterus salmoides through necroptosis - Zheng-Yang Zhou; Sheng-Yu He; Chen-Wang Lu; Shang-Jie Bai; Lin-Feng Kuang; Bin Yang; Sheng Lian; Zheng-Ran Jian; Meng-Meng Wang; Shuang-Yan Xiao; Qing Yu; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Uptake, accumulation and toxicity of short chain chlorinated paraffins to wheat (Triticum aestivum L.) - Jianzhong Yu; Qing Tang; Ge Yin; Weifang Chen; Jitao Lv; Lingxiangyu Li; Chenghao Zhang; Yunxiang Ye; Xijiao Song; Xueping Zhao; Tao Tang; Changpeng Zhang; et al. (Journal of Hazardous Materials, 2024)

Production of carbon nanotubes via catalytic pyrolysis of polyethylene over Ni/ZSM-5 prepared by ethylene glycol assisted impregnation - Qing-Lin Li; Rui Shan; Shu-Xiao Wang; Tao-li Huhe; Hao-Ran Yuan; Yong Chen (Fuel, 2024)

Bright photoactivatable probes based on triphenylethylene for Cu2+ detection in tap water and tea samples - Zuo-Qin Liang; Dong-Dong Song; Zhuo-Cheng Li; Su-Hang Xu; Guo-Liang Dai; Chang-Qing Ye; Xiao-Mei Wang; Xu-Tang Tao (Food Chemistry, 2024)

Comparative analysis of key precursors and metabolites involved in flavor formation of different rapid-fermented Chinese fish sauces based on untargeted metabolomics analysis - Jiarun Han; Jialan Jiang; Xin Zhao; Xilian Zhao; Tao Kong; Ping Li; Qing Gu (Food Chemistry, 2024)

Growth characteristics and biomass model of Cupressus gigantea sapling - Liu Chang-Sheng; Li Tao; Zhang Rui-wen; Wang Chao; Qu Xing-le; Luo Da-qing (Trees, 2024)

Human Bone Marrow Derived-Mesenchymal Stem Cells Treatment for Autoimmune Premature Ovarian Insufficiency - Wen-Qing Ma; Ai-Ping Zhuo; Yuan-Ling Xiao; Meng Gao; Yu-Tao Yang; Li-Chao Tang; Yan-Hong Wu; Dan Tian; Xia-Fei Fu (Stem Cell Reviews and Reports, 2024)

Histone methyltransferase KMT2D inhibits ENKTL carcinogenesis by epigenetically activating SGK1 and SOCS1 - Yue-Hua Zhang; Qing Tao; Wen-Yan Zhang; Sha Zhao; Wei-Ping Liu; Li-Min Gao (Genes & Genomics, 2024)

Dependency analysis method for human failure events in level 2 probabilistic safety assessment of nuclear power plants - Shuai Chen; Zehuan Zhang; Tao Qing; Li Zhang (Annals of Nuclear Energy, 2024)

A pair of new chromone enantiomers from Xylaria nigripes - Jing Li; Yue-Ping Jiang; Lan-Qing Li; Hong-Ping Long; Hai-Tao Liu; Rong Yang; Shao Liu; Wen-Xuan Wang; Ji-Kai Liu (Natural Product Research, 2024)

Nanosuspensions as an approach for improved solubility and anti-Ichthyophthirius multifiliis activity of magnolol - Jietao Liu; Shenye Qu; Tao Wang; Bin Yang; Xiang Liu; Gaoxue Wang; Pengfei Li; Qing Yu; Fei Ling (Aquaculture, 2024)

Study on Airflow Distribution and Energy Conservation in a BSL-4 Laboratory Involved in Aerosol Infection Risk - Jianmei Zhong; Wei Zhang; Xiaoli Wang; Jinsheng Zhan; Tao Xia; Lingzhi Xie; Xiding Zeng; Kun Yang; Zhangyu Li; Ruiwen Zou; Zepu Bai; Qing Wang; et al. (Sustainable Cities and Society, 2024)

Sirtuin 3-mediated deacetylation of superoxide dismutase 2 ameliorates sodium fluoride-induced mitochondrial dysfunction in porcine oocytes - Xin-Yue Qi; Jin-Dong Yuan; Zi-Yu Liu; Xi-Qing Jiang; Qi Zhang; Shan-Long Zhang; Lu Zhao; Ling-Yan Ke; Chen-Yuan Zhang; Yan Li; Lu-Yan Zhang; Qian-Qian Xu; et al. (Science of The Total Environment, 2024)

The joint action of biochar and plant roots on U-stressed soil remediation: Insights from bacteriomics and metabolomics - Nan Li; Yilin Wang; Li Zhou; Dengjiang Fu; Tao Chen; Xiaoming Chen; Qing Wang; Wenkun Zhu (Journal of Hazardous Materials, 2024)

A nanocarrier immersion vaccine encoding surface immunogenic protein confers cross-immunoprotection against Streptococcus agalactiae and Streptococcus iniae infection in tilapia - Ye Cao; Jia Liu; Gaoyang Liu; Hui Du; Tianqiang Liu; Tao Liu; Pengfei Li; Qing Yu; Gaoxue Wang; Erlong Wang (Fish & Shellfish Immunology, 2024)

Potentiation of the lateral habenula-ventral tegmental area pathway underlines the susceptibility to depression in mice with chronic pain - Chun-Kui Zhang; Pan Wang; Yuan-Yuan Ji; Jian-Shuai Zhao; Jun-Xiang Gu; Xian-Xia Yan; Hong-Wei Fan; Ming-Ming Zhang; Yu Qiao; Xiao-Die Liu; Bao-Juan Li; Ming-Hui Wang; et al. (Science China Life Sciences, 2024)

Plasma membrane-localized hexose transporter OsSWEET1b, affects sugar metabolism and leaf senescence - Qiang Zhang; Changzhao Chen; Rui Guo; Xiaofang Zhu; Xinyu Tao; Mengxing He; Zhiwen Li; Lan Shen; Qing Li; Deyong Ren; Jiang Hu; Li Zhu; et al. (Plant Cell Reports, 2024)

Kaempferol and ginsenoside Rg1 ameliorate acute hypobaric hypoxia induced lung injury based on network pharmacology analysis - Na Li; Yuan Cheng; Tao Jin; Lirui Cao; Jieyu Zha; Xiong Zhu; Qing He (Toxicology and Applied Pharmacology, 2023)

Metagenome-assembled genomes reveal carbohydrate degradation and element metabolism of microorganisms inhabiting Tengchong hot springs, China - Zhufeng Zhang; Tao Liu; Xudong Li; Qing Ye; Hina Iqbal Bangash; Jinshui Zheng; Nan Peng (Environmental Research, 2023)

Serum Cu, Zn and IL–1β Levels May Predict Fetal Miscarriage Risk After IVF Cycles: A Nested Case–Control Study - Yuan Hu; Dongyang Zhang; Qing Zhang; Tao Yin; Tingting Jiang; Shitao He; Mengzhu Li; Xinyu Yue; Guiying Luo; Fangbiao Tao; Yunxia Cao; Dongmei Ji; et al. (Biological Trace Element Research, 2023)

Triptolide induces PANoptosis in macrophages and causes organ injury in mice - Hong-Rui Zhang; Ya-Ping Li; Zi-Jian Shi; Qi-Qi Liang; Si-Yuan Chen; Yi-Ping You; Tao Yuan; Rong Xu; Li-Hui Xu; Dong-Yun Ouyang; Qing-Bing Zha; Xian-Hui He (Apoptosis, 2023)

Distinct and shared endothermic strategies in the heat producing tissues of tuna and other teleosts - Baosheng Wu; Xueli Gao; Mingling Hu; Jing Hu; Tianming Lan; Tingfeng Xue; Wenjie Xu; Chenglong Zhu; Yuan Yuan; Jiangmin Zheng; Tao Qin; Peidong Xin; et al. (Science China Life Sciences, 2023)

Locating the Scope and Depth of Coal Fires Based on Magnetic and Electrical Data - Zhenlu Shao; Guofu Zhang; Tao Zhou; Jun Wei; Fei Cao; Yong Zhang; Hongsheng Li; Huahai Sun; Shangkun Qing; Teng Chen; Long Chen; Hongwen Shao; et al. (Pure and Applied Geophysics, 2023)

Arbuscular mycorrhiza changes plant facilitation patterns and increases resource use efficiency in intercropped annual plants - Shuang-Guo Zhu; Hai-Xia Duan; Hong-Yan Tao; Li Zhu; Rui Zhou; Yu-Miao Yang; Xiao-Lin Zhang; Wen-Ying Wang; Hao Zhu; Wei Zhang; Ren-Qing Wang; Xiu-Ping Tao; et al. (Applied Soil Ecology, 2023)

Fundicoccus culcitae sp. nov., a novel potential bacteriocin producing bacterium isolated from a spoiled eye mask - Gang Zhou; Lei Gao; Bao-Zhu Fang; Ying-Si Wang; Hong-Bing Tao; Xia Wen; Qian Wang; Xiao-Mo Huang; Qing-Shan Shi; Wen-Jun Li; Xiao-Bao Xie (Antonie van Leeuwenhoek, 2023)

Regulation of microbial metabolism on the formation of characteristic flavor and quality formation in the traditional fish sauce during fermentation: a review - Jiarun Han; Tao Kong; Qi Wang; Jialan Jiang; Qingqing Zhou; Ping Li; Beiwei Zhu; Qing Gu (Critical Reviews in Food Science and Nutrition, 2023)

Understanding the mechanism underlying the anti-diabetic effect of dietary component: a focus on gut microbiota - Yuhan Zhao; Mengjie Li; Yanan Wang; Ruixuan Geng; Jingjing Fang; Qing Liu; Seong-Gook Kang; Wei Cai Zeng; Kunlun Huang; Tao Tong (Critical Reviews in Food Science and Nutrition, 2023)

Maternal transfer of F-53B inhibited neurobehavior in zebrafish offspring larvae and potential mechanisms: Dopaminergic dysfunction, eye development defects and disrupted calcium homeostasis - Luyin Wu; Mohammed Zeeshan; Yao Dang; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Li-Hao Guo; Yuan-Yuan Fan; Ming-Kun Sun; Tao Yu; Yue Wen; et al. (Science of The Total Environment, 2023)

Synergistic driving effects of risk factors on human brucellosis in Datong City, China: A dynamic perspective from spatial heterogeneity - Li Shen; Ming-hao Sun; Wen-tao Ma; Qing-wu Hu; Chen-xi Zhao; Zu-rong Yang; Cheng-hao Jiang; Zhong-jun Shao; Kun Liu (Science of The Total Environment, 2023)

Coupled responses of the flow-induced vibration and flow-induced rotation of a rigid cylinder-plate body - Tao Tang; Hongjun Zhu; Qing Xiao; Quanyu Chen; Jiawen Zhong; Yingmei Li; Tongming Zhou (Ocean Engineering, 2023)

Enhanced nitrogen removal in a pilot-scale AOA-SBFASR system treating municipal wastewater: Process efficiency, microbial community and nitrogen metabolic pathways - Zhi-li Du; Shao-bin Huang; Rui-jian Zhang; Yong-qing Zhang; Hao-tao Dong; Guang-hua Wang; Zhi-min Sun (Journal of Water Process Engineering, 2023)

High throughput, antibacterial and nonflammable melamine sponges for oil/water separation - Yu Li; Shusu Ren; Qing Yu; Tao Wang; Xiang Xu; Weiwei He; Lifen Zhang; Zhenping Cheng (Journal of Environmental Chemical Engineering, 2023)

Efficient removal of Cr(VI) from wastewater by ZnO-polyacrylic acid/cellulose fiber/polyethylene glycol hydrogel: Synergistic effect of adsorption and photocatalytic reduction - Qing Li; Xiaojie Zhuang; Guanhong Zhou; Zhenfei Yang; Ting Yang; Hongbo Xiao; Tao Xu; Wenlei Wang (Journal of Environmental Chemical Engineering, 2023)

Chemical constituents from the leaves of Callicarpa arborea Roxb. and their chemotaxonomic significance - Tao-Li Zhang; Qiao-Qi Yi; Yu-Xiao Han; Lu Zhao; Shu-Qing Gui; Wen-Xia Liu; Hong-Gang Wang (Biochemical Systematics and Ecology, 2023)

GABAergic Neurons in the Nucleus Accumbens are Involved in the General Anesthesia Effect of Propofol - Jing Yan; Bei-Ning Hang; Lin-Hui Ma; Jia-Tao Lin; Yue Zhou; Xin-Hao Jiao; Ying-Xuan Yuan; Ke-Jie Shao; Le-Meng Zhang; Qi Xue; Zi-Yi Li; Hong-Xing Zhang; et al. (Molecular Neurobiology, 2023)

Modeling of breaching parameters for debris flow dams - He-chun Ruan; Hua-yong Chen; Xiao-qing Chen; Wan-yu Zhao; Jian-gang Chen; Tao Wang; Yao Jiang; Xi-an Wang; Xiang-ning Li; Xiao Li; Yun-han Yu (Journal of Mountain Science, 2023)

Study on the thermal release characteristics and the correlation transformation mechanism of microscopic active groups of oxidized coal combustion in a deep mined-out area - Hui-yong Niu; Qing-qing Sun; Shuo-peng Li; Si-wei Sun; Yun-chuan Bu; Yan-xiao Yang; Zi-hao Mao; Meng Tao (Science of The Total Environment, 2023)

Analytical behavior and bearing capacity research on out-of-code tapered CFDST members under pure torsion and compression-torsion combination - Jian-Tao Wang; Xiang-Hong Liu; Qing Sun; Yu-Wei Li (Ocean Engineering, 2023)

Novel facile synthesis and room-temperature sintering of copper nanowires for solution-processed transparent conductive films - Qing Liu; Yibo Wu; Yong Li; Yuling Shi; Qianqian Pan; Danlong Yang; Tao Wang (Chemical Engineering Journal, 2023)

Study on the characteristics of actinic radiation and direct aerosol radiation effects in the Pearl River Delta region - Tao Deng; Yu Zou; Sheng Hu; Fei Li; Guowen He; Shanshan Ouyang; Xue Zhang; Qing Wang; Zebiao Zhang; Boru Mai; Li Liu; Luyao Zhang; et al. (Atmospheric Environment, 2023)

The associations of non-essential metal mixture with fasting plasma glucose among Chinese older adults without diabetes - Jing-Yuan Lei; Pan-Pan Wang; Hong-Li Wang; Yuan Wang; Liang Sun; Bing Hu; Su-Fang Wang; Dong-Mei Zhang; Gui-Mei Chen; Chun-Mei Liang; Fang-Biao Tao; Lin-Sheng Yang; et al. (Environmental Science and Pollution Research, 2023)

Compressive–Flexural Failure Mechanism and Bearing Capacity Calculation of Over-Ranging Tapered CFDST Members for Support Structures of Offshore Wind Turbines - Jian-Tao Wang; Xiang-Hong Liu; Qing Sun; Yu-Wei Li (Journal of Marine Science and Engineering, 2023)
Upon the higher requirement on high-performance structures of large-scale supporting structures of offshore wind turbines, the systematic analysis on the compressive-flexural behavior and ultimate bearing capacity of tapered concrete-filled double skin steel tubular (CFDST) members designed by over-ranging parameters was performed. Investigating the entire-process mechanism, e.g., the moment–deformation response, stress development, interaction stress, and subassembly contribution, was based on the finite element (FE) analysis, where the moment–deformation curve can be distinguished by four characteristic points, and the transverse local buckling of outer tube partly weakens distribution height of interface pressure in compression zone compared to that in tension zone. Influences of material strengths and geometric parameters were examined by the parametric study, e.g., increasing tapered angle (ψ) slightly reduces the bearing capacity; the higher axial compression ratio (n) contributes a noteworthy action on the post-peak behavior and carrying capacity, e.g., the bearing capacities at n = 0.9 and n = 0.5 reduce by 64.14% and 18.44% compared to capacity at n = 0.1, respectively; influence of Do/to ratio is more significant than Di/ti ratio. Subsequently, the modified cross-sectional stress integration (CSI) method was proposed to predict the moment–strain (M-ε) curves of tapered CFDST members; meanwhile, a confined concrete model with transverse confinement stress as an explicit parameter was modified, and influences of different confined concrete models on predicting M-ε curves were compared. Finally, design methods based on the modified CSI method and limit state method were proposed as a simplified calculation method to determine the correlative relationship of axial compressive strength and moment-resisting capacity (N-M curve).

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Investigation of the peak punch-through capacity of spudcan on sand overlying spatially variable clay - Jiang Tao Yi; Shi Jie Xu; Xiao Bin Li; Qing Shan Yang; Si Yu Li (Ocean Engineering, 2023)

Comparative analysis of volatile compounds and microbial community succession in Chinese fish sauce: Three typical types of fast-fermented fish sauces - Jiarun Han; Jialan Jiang; Tao Kong; Xilian Zhao; Xin Zhao; Ping Li; Qing Gu (Food Bioscience, 2023)

High prevalence and genomic characteristics of carbapenem-resistant Enterobacteriaceae and colistin-resistant Enterobacteriaceae from large-scale rivers in China - Cai-Hong Guo; Yu-Qing Liu; Yan Li; Xiao-Xiao Duan; Ting-Yu Yang; Fang-Yu Li; Ming Zou; Bao-Tao Liu (Environmental Pollution, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Damage identification method on shield tunnel based on PLSR and equivalent damage analysis - Zhi-guo Yan; Jian-tao Li; Yi Shen; Zi-qi Xiao; Qing Ai; He-hua Zhu (Tunnelling and Underground Space Technology, 2023)

Experimental and analytical research on seismic performance of ECC-filled high-strength double skin steel tubular columns with out-of-code D/t ratios - Jian-Tao Wang; Yu-Wei Li; Qing Sun; Xiang-Hong Liu (Ocean Engineering, 2023)

The bound polyphenols of foxtail millet (Setaria italica) inner shell inhibit breast cancer by promoting lipid accumulation-induced autophagic death - Li-chao Zhang; Ya-ning Liu; Xiao-qin La; Shuai-tao Li; Li-na Wen; Ting Liu; Han-qing Li; Ai-ping Li; Haitao Wu; Chang-xin Wu; Zhuo-yu Li (Food and Chemical Toxicology, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

OrMKK3 Influences Morphology and Grain Size in Rice - Ying Hua Pan; Li Jun Gao; Yun Tao Liang; Yan Zhao; Hai Fu Liang; Wei Wei Chen; Xing Hai Yang; Dong Jin Qing; Ju Gao; Hao Wu; Juan Huang; Wei Yong Zhou; et al. (Journal of Plant Biology, 2023)

Unraveling the evolution of dissolved organic matter in full-scale A/A/O wastewater treatment process using size exclusion chromatography with PARAFAC and nonnegative matrix factorization analysis - Min-Hui Cai; Ye-Chao Tian; Ai-Min Li; Yan Li; Yu-Ze Han; Wen-Xiang Ji; Qing Zhou; Jun Li; Wen-Tao Li (Water Research, 2023)

Toxicity mechanism of peri-implantation pesticide beta-cypermethrin exposure on endometrial remodeling in early pregnant mice - Yong-Jiang Zhou; Qian-Feng Qiao; Li-Qing Wang; Tao-Yu Sheng; Man-Xue Cui; Qi-Duo Chen; Can-Yang Wang; Yun-Xiao Zhang (Toxicology, 2023)

Soil organic carbon stability mediate soil phosphorus in greenhouse vegetable soil by shifting phoD-harboring bacterial communities and keystone taxa - Shuo Chen; Liying Wang; Shuai Zhang; Naihui Li; Xiaomeng Wei; Yuquan Wei; Lulu Wei; Ji Li; Shaowen Huang; Qing Chen; Tao Zhang; Nanthi S. Bolan (Science of The Total Environment, 2023)

Machine learning based age-authentication assisted by chemo-kinetics: Case study of strong-flavor Chinese Baijiu - Qing-Ru Liu; Xiao-Juan Zhang; Lei Zheng; Lian-Jun Meng; Guang-Qian Liu; Ting Yang; Zhen-Ming Lu; Li-Juan Chai; Song-Tao Wang; Jin-Song Shi; Cai-Hong Shen; Zheng-Hong Xu (Food Research International, 2023)

Incorporating CdS and anchoring Pt single atoms into porphyrinic metal–organic frameworks for superior visible-light and sunlight-driven H2 evolution - Guo-Wei Guan; Su-Tao Zheng; Mengyang Xia; Ke-Xin Li; Yi-Shan Ouyang; Guidong Yang; Qing-Yuan Yang (Chemical Engineering Journal, 2023)

The effect of phthalates exposure during pregnancy on asthma in infants aged 0 to 36 months: a birth cohort study - Jian-Qing Wang; Chun-Mei Liang; Ya-Bin Hu; Xun Xia; Zhi-Juan Li; Hui Gao; Jie Sheng; Kun Huang; Su-Fang Wang; Peng Zhu; Jia-Hu Hao; Fang-Biao Tao (Environmental Geochemistry and Health, 2023)

One-step extraction and solidification of uranium (VI) from sulfate leaching liquor using bifunctional ionic liquids - Fang Zhang; Qiang Wu; Jia-Xuan Yan; Lei-Tao Sha; Yang Li; Xu-Xin Li; Qing-Gang Huang; Ze-Yi Yan (Journal of Environmental Chemical Engineering, 2023)

Click-crosslinked in-situ hydrogel improves the therapeutic effect in wound infections through antibacterial, antioxidant and anti-inflammatory activities - Xiong-Xin Lei; Chen-Yu Zou; Juan-Juan Hu; Yan-Lin Jiang; Xiu-Zhen Zhang; Long-Mei Zhao; Tao He; Qing-Yi Zhang; Ya-Xing Li; Jesse Li-Ling; Hui-Qi Xie (Chemical Engineering Journal, 2023)

Ecotoxicity stress and bioaccumulation in Eisenia fetida earthworms exposed to vanadium pentoxide in soil - Shi-qing Zhao; Hong Ni; Ji Li; Shun-hao Ai; Xiao-nan Wang; Xiang-yun Gao; Qian-yun Xu; Zheng-tao Liu (Environmental Science and Pollution Research, 2023)

Effect of feeding level on growth, digestive and metabolic enzymes and antioxidant capacity in juvenile Yangtze sturgeon (Acipenser dabryanus) - Bin He; Bo Zhou; Hang Xie; Zeng-Tan Hu; Bin Wang; Jun-Lin Zhang; Qing-Zhi Li; Feng-Qi Zhao; Xing Liu; Qian-Dong Li; Tao Yan (Aquaculture, 2023)

Early Neoproterozoic well-preserved stromatolites from southern Liaoning, North China: characteristics and paleogeographic implications - Yong-Li Zhang; Guan-Ming Lai; En-Pu Gong; Mark A. Wilson; Wen-Tao Huang; Chang-Qing Guan; Ding-Cheng Yuan (Palaeoworld, 2023)

The genomes of medicinal skullcaps reveal the polyphyletic origins of clerodane diterpene biosynthesis in the family Lamiaceae - Haixiu Li; Song Wu; Ruoxi Lin; Yiren Xiao; Ana Luisa Malaco Morotti; Ya Wang; Meytal Galilee; Haowen Qin; Tao Huang; Yong Zhao; Xun Zhou; Jun Yang; et al. (Molecular Plant, 2023)

Simultaneous determination of dissolved organic nitrogen, nitrite, nitrate and ammonia using size exclusion chromatography coupled with nitrogen detector - Wen-Xiang Ji; Ye-Chao Tian; Min-Hui Cai; Bi-Cun Jiang; Shi Cheng; Yan Li; Qing Zhou; Bo-Qiang Li; Bai-Yang Chen; Xing Zheng; Wen-Tao Li; Ai-Min Li (Journal of Environmental Sciences, 2023)

Sustainable processing of gold cyanide tailings: Reduction roasting, mechanical activation, non-cyanide leaching, and magnetic separation - Lei Zhang; Tao Jiang; Xue-yi Guo; Qing-hua Tian; Shui-ping Zhong; Li Dong; Hong Qin; Zuo-wei Liu; Brian Makuza (Hydrometallurgy, 2023)

Molecular characterization of a teleost-specific toll-like receptor 22 (tlr22) gene from yellow catfish (Pelteobagrus fulvidraco) and its transcriptional change in response to poly I:C and Aeromonas hydrophila stimuli - Xiu-Ying Wei; Jun Wang; Sheng-Tao Guo; Yun-Yun Lv; Yan-Ping Li; Chuan-Jie Qin; Yuan-Chao Zou; Qing-Chao Shi; Peng Hu; Xiao-Qin Xiong; Yang He; Rui Li; et al. (Fish & Shellfish Immunology, 2023)

Re-recognizing fluorescence quenching Units: Improve abnormally the luminescent efficiency of AIEgens for fluorescence Sensing, organelle targeted imaging and photodynamic therapy - Muzhou Teng; Jialin Tong; Yili Xie; Yumin Li; Zhijia Li; Guogang Shan; Yin Li; Qing Wan; Zhiming Wang; Tao Liu (Chemical Engineering Journal, 2023)

Distribution patterns of landslides triggered by the 2022 Ms 6.8 Luding earthquake, Sichuan, China - Jian-qiang Zhang; Zong-ji Yang; Qing-kai Meng; Jiao Wang; Kai-heng Hu; Yong-gang Ge; Feng-huan Su; Bo Zhao; Bo Zhang; Ning Jiang; Yu Huang; Zai-yang Ming; et al. (Journal of Mountain Science, 2023)

Identification and pathogenetic study of tilapia lake virus (TiLV) isolated from naturally diseased tilapia - Tao He; Yu-Zhou Zhang; Li-Hong Gao; Bo Miao; Ji-Shu Zheng; De-Cheng Pu; Qing-Qing Zhang; Wei-Wei Zeng; De-Shou Wang; Sheng-Qi Su; Song Zhu (Aquaculture, 2023)

Macroevolutionary analyses point to a key role of hosts in diversification of the highly speciose eriophyoid mite superfamily - Xiao-Feng Xue; Liang-Fei Yao; Yue Yin; Qing Liu; Ni Li; Ary A. Hoffmann; Jing-Tao Sun; Xiao-Yue Hong (Molecular Phylogenetics and Evolution, 2023)

Co-substrate promoting the biodegradation of refractory DOM in semi-coking wastewater: DOM evolution and microbial community - Min-Hui Cai; Ye-Chao Tian; Ai-Min Li; Yan Li; Yu-Ze Han; Jun Li; Hong-Fang Sun; Xin Wang; Qing Zhou; Wen-Tao Li (Journal of Environmental Chemical Engineering, 2023)

Effect of Tribute citrus essential oil nanoemulsion-loaded gelatin on the gel behavior and gelation surface morphologies - Guoqiang Li; Qingqing Zhou; Shuxun Liu; Cheng Qian; Jiarun Han; Tao Zhou; Ping Li; Qing Gu (Food Bioscience, 2023)

Different roles of primary and secondary sources in reducing PM2.5: Insights from molecular markers in Pearl River Delta, South China - Kong Yang; Duo-Hong Chen; Xiang Ding; Jun Li; Yu-Qing Zhang; Tao Zhang; Qiao-Yun Wang; Jun-Qi Wang; Qian Cheng; Hao Jiang; Ping Liu; Zi-Rui Wang; et al. (Atmospheric Environment, 2023)

In situ phytostabilization of arable soils severely contaminated with cadmium at Yangshuo, Southern China, using cash crops and amendments: a comprehensive performance evaluation - Bo-Fang Yan; Mei-Lin Yan; Xue Xiao; Rong-Liang Qiu; Yuan-Qing Chao; Yin-Xin Li; Su-Lian Lv; Zhong-Xin Tan; Ye-Tao Tang (Journal of Soils and Sediments, 2023)

Water microecology is affected by seasons but not sediments: A spatiotemporal dynamics survey of bacterial community composition in Lake Changshou—The largest artificial lake in southwest China - Ai-ling Chen; Fu-qing Xu; Xia Su; Fu-pan Zhang; Wan-chao Tian; Shang-jie Chen; Fang Gou; Zhi-lin Xing; Jin-xin Xiang; Juan Li; Tian-tao Zhao (Marine Pollution Bulletin, 2023)

Bioregulation of FeNi LDH morphology and electronic structure to highly promote electrocatalytic oxygen evolution - Guang Li; Chang Liu; Yun Yang; Xiuwen Pan; Tao Wu; Feng Zeng; Enyang Ma; Qing Qu; Lei Li (Chemical Engineering Journal, 2023)

Exposure–response relationship between temperature, relative humidity, and varicella: a multicity study in South China - Yihan Li; Jialing Li; Zhihua Zhu; Weilin Zeng; Qi Zhu; Zuhua Rong; Jianxiong Hu; Xing Li; Guanhao He; Jianguo Zhao; Lihua Yin; Yi Quan; et al. (Environmental Science and Pollution Research, 2023)

Parameter identification and state estimation for nuclear reactor operation digital twin - Helin Gong; Tao Zhu; Zhang Chen; Yaping Wan; Qing Li (Annals of Nuclear Energy, 2023)

Overexpression of α-Tubulin Gene of Sugarcane (Saccharum spp. hybrids), SoTUA, Enhances Tobacco Tolerance to Cold Stress - Jiao-Yun Chen; Bo Sun; Qaisar Khan; Li-Tao Yang; Bao-Qing Zhang; Yong-Xiu Xing; Yang-Rui Li (Sugar Tech, 2022)

Inhibition of Microglial NLRP3 with MCC950 Attenuates Microglial Morphology and NLRP3/Caspase-1/IL-1β Signaling In Stress-induced Mice - Qing Liu; Man-Man Zhang; Min-Xia Guo; Qiu-Ping Zhang; Na-Zhi Li; Jie Cheng; Shi-Le Wang; Guang-Hui Xu; Cheng-Fu Li; Ji-Xiao Zhu; Li-Tao Yi (Journal of Neuroimmune Pharmacology, 2022)

GDH promotes isoprenaline-induced cardiac hypertrophy by activating mTOR signaling via elevation of α-ketoglutarate level - Zhi-Rong Lin; Zhen-Zhen Li; Yan-Jun Cao; Wen-Jing Yu; Jian-Tao Ye; Pei-Qing Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)

Evolution mechanism and deformation stability analysis of rock slope block toppling for early warnings - Jian-qiao Mu; Tian-tao Li; Xiang-jun Pei; Run-qiu Huang; Fu-an Lan; Xue-qing Zou (Natural Hazards, 2022)

Dynamic effects of short-term exercise on muscle texture and gut flora in the hybrid (Megalobrama amblycephala♀ × Ancherythroculter nigrocauda♂) - Huijie Wei; Lang Zhang; Qing Li; Yali Yu; Yanhong Sun; Ziwei Song; Pei Li; Tao Mao; Jian Chen; Li He; Guiying Wang (Frontiers in Marine Science, 2022)
Fillet texture plays a significant role in consumer acceptance, which heavily influenced by exercise according to previous studies. “Xianfeng No. 2”, a novel hybrid of Megalobrama amblycephala ( M. amblycephala ) (♀) and Ancherythroculter nigrocauda ( A. nigrocauda ) (♂), with characteristics of quick growth, good disease resistance, and anti-stress capability, is one of an important aquaculture fish species in China, however, the ways to improve fillet quality in this species remains unknown. In this study, a short-term exercise trial (0-16d), hematoxylin and eosin (H&E) staining, and texture analysis were carried out to determine the effects of exercise on muscle cellularity and texture. Furthermore, 16S rRNA analysis was performed to determine the impacts of exercise on the intestinal microbiota. Compared with non-exercised group (0d), exercised groups showed influences in muscle cellularity (decreased muscle fiber diameter and increased muscle fiber density) and improvements in muscle texture (increased hardness, cohesiveness, gumminess, and chewiness). In addition, 16S rRNA sequencing analysis exhibited that short-term exercise could significantly increase the community richness and diversity, as well as alter the composition of gut microflora in this hybrid species. At the level of phylum, the relative richness of Proteobacteria , Firmicutes , Bacteroidetes , and Fusobacteria changed remarkably after short-term exercise. At the level of genus, the relative richness of Pseudomonas , Acinetobacter , Stenotrophomonas , Alpinimonas , Rhodococcus , Shewanella , Brevundimonas changed significantly, suggested that short-term swimming exercise might increase intrinsic antimicrobial resistance and promote denitrification capacity of this hybrid species. Furthermore, a LEfSe analysis of intestinal microflora communities illustrated that Pseudomonas and MNG7 may be utilized to distinguish between exercised and non-exercised fish. Our research, collectively, found an effective way to improve fillet texture by exercise, revealed the impacts of exercise on the intestinal microbiota, further expanded our knowledge of fish under exercise.

Truncated analog Brevinin2-CE-N26V5K: Revelation the Augmentation of Antimicrobial Activity - Yi Zhao; Xiao-yan Wang; Yan Sun; Zhi Li; Tao Liu; Qing-mei Liu; Jingyi Chen (World Journal of Microbiology and Biotechnology, 2022)

Mechanisms underlying microRNA-222-3p modulation of methamphetamine-induced conditioned place preference in the nucleus accumbens in mice - Qing Shang; Jing Wang; Zhijia Xi; Baoyao Gao; Hongyan Qian; Ran An; Gaojie Shao; Hua Liu; Tao Li; Xinshe Liu (Psychopharmacology, 2022)

Recyclable structured toxic industrial nickel-containing sludge for efficient anionic contaminant adsorption - Qiong Tian; Zhipeng Lin; Fengxian Qiu; Zhangdi Li; Qing Guo; Tao Zhang (Environmental Science and Pollution Research, 2022)

Geochronological, geochemical, and P–T path constraints on the late Paleoproterozoic continent–continent collision orogeny in the Quruqtagh Block, Tarim Craton - Tao Cui; Shan-Shan Li; Rui-Qing Guo; Germain Bishikwabo; Xiang-Kuan Gong; Gui-Ping Liu; Yu Guo (Arabian Journal of Geosciences, 2022)

Identification and validation of quantitative trait loci for the functional stay green trait in common wheat (Triticum aestivum L.) via high-density SNP-based genotyping - Tianheng Ren; Tao Fan; Shulin Chen; Yongyan Chen; Xia Ou; Qing Jiang; Wanhua Peng; Zhenglong Ren; Feiquan Tan; Peigao Luo; Zhi Li (Theoretical and Applied Genetics, 2022)

Anterior Cingulate Cortex Mediates Hyperalgesia and Anxiety Induced by Chronic Pancreatitis in Rats - Dan Ren; Jia-Ni Li; Xin-Tong Qiu; Fa-Ping Wan; Zhen-Yu Wu; Bo-Yuan Fan; Ming-Ming Zhang; Tao Chen; Hui Li; Yang Bai; Yun-Qing Li (Neuroscience Bulletin, 2022)
Central sensitization is essential in maintaining chronic pain induced by chronic pancreatitis (CP), but cortical modulation of painful CP remains elusive. Here, we examined the role of the anterior cingulate cortex (ACC) in the pathogenesis of abdominal hyperalgesia in a rat model of CP induced by intraductal administration of trinitrobenzene sulfonic acid (TNBS). TNBS treatment resulted in long-term abdominal hyperalgesia and anxiety in rats. Morphological data indicated that painful CP induced a significant increase in FOS-expressing neurons in the nucleus tractus solitarii (NTS) and ACC, and some FOS-expressing neurons in the NTS projected to the ACC. In addition, a larger portion of ascending fibers from the NTS innervated pyramidal neurons, the neural subpopulation primarily expressing FOS under the condition of painful CP, rather than GABAergic neurons within the ACC. CP rats showed increased expression of vesicular glutamate transporter 1, and increased membrane trafficking and phosphorylation of the N -methyl-D-aspartate receptor (NMDAR) subunit NR2B and the α-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid receptor (AMPAR) subunit GluR1 within the ACC. Microinjection of NMDAR and AMPAR antagonists into the ACC to block excitatory synaptic transmission significantly attenuated abdominal hyperalgesia in CP rats, which was similar to the analgesic effect of endomorphins injected into the ACC. Specifically inhibiting the excitability of ACC pyramidal cells via chemogenetics reduced both hyperalgesia and comorbid anxiety, whereas activating these neurons via optogenetics failed to aggravate hyperalgesia and anxiety in CP rats. Taken together, these findings provide neurocircuit, biochemical, and behavioral evidence for involvement of the ACC in hyperalgesia and anxiety in CP rats, as well as novel insights into the cortical modulation of painful CP, and highlights the ACC as a potential target for neuromodulatory interventions in the treatment of painful CP.

Short-term effect of ambient air pollutant change on the risk of tuberculosis outpatient visits: a time-series study in Fuyang, China - Xin-Qiang Wang; Ying-Qing Li; Cheng-Yang Hu; Kai Huang; Kun Ding; Xiao-Jing Yang; Xin Cheng; Kang-Di Zhang; Wen-Jie Yu; Jie Wang; Yong-Zhong Zhang; Zhen-tao Ding; et al. (Environmental Science and Pollution Research, 2022)

Aberrant functional and effective connectivity of the frontostriatal network in unilateral acute tinnitus patients with hearing loss - Gang-Ping Zhou; Yu-Chen Chen; Wang-Wei Li; Heng-Le Wei; Yu-Sheng Yu; Qing-Qing Zhou; Xindao Yin; Yue-Jin Tao; Hong Zhang (Brain Imaging and Behavior, 2022)

Nitric Oxide Signaling Pathway in Ventral Tegmental Area is Involved in Regulation of 7,8-Dihydroxyflavone on Alcohol Consumption in Rats - Qing Gao; Tao Yang; Xin-Xin Li; Jun-Wei Xiong; Wei Ma; Yan-Min Xu; Yong Liu; Hong-Yan Zhang; Qi-Yu Wang; Hong-Xuan Wang; Ying Peng; Xiao-Feng Zhu; et al. (Molecular Neurobiology, 2022)

Deinococcus aestuarii sp. nov. and Deinococcus aquaedulcis sp. nov., two novel resistant bacteria isolated from pearl river estuary - Ling-Zi Yin; Jia-Ling Li; Ze-Tao Liu; Bao-Zhu Fang; Pandeng Wang; Xiao-Qing Luo; Lei Dong; Li Duan; Shan-Hui Li; Wen-Jun Li (Antonie van Leeuwenhoek, 2022)

Colorado geoid computation experiment: overview and summary - Yan Ming Wang; Laura Sánchez; Jonas Ågren; Jianliang Huang; René Forsberg; Hussein A. Abd-Elmotaal; Kevin Ahlgren; Riccardo Barzaghi; Tomislav Bašić; Daniela Carrion; Sten Claessens; Bihter Erol; et al. (Journal of Geodesy, 2021)

MicroRNA-31-3p/RhoA signaling in the dorsal hippocampus modulates methamphetamine-induced conditioned place preference in mice - Hongyan Qian; Qing Shang; Min Liang; Baoyao Gao; Jing Xiao; Jing Wang; Axiang Li; Canyu Yang; Jianmin Yin; Gang Chen; Tao Li; Xinshe Liu (Psychopharmacology, 2021)

The occurrence order and cross-talk of different tRNA modifications - Jing Li; Wen-Yu Zhu; Wen-Qing Yang; Cai-Tao Li; Ru-Juan Liu (Science China Life Sciences, 2021)

Association between large artery stenosis, cerebral small vessel disease and risk of ischemic stroke - Fei Han; Ding-Ding Zhang; Fei-Fei Zhai; Jun Xue; Jiang-Tao Zhang; Shuang Yan; Li-Xin Zhou; Jun Ni; Ming Yao; Meng Yang; Ming-Li Li; Zheng-Yu Jin; et al. (Science China Life Sciences, 2021)

Overexpression of SoACLA-1 Gene Confers Drought Tolerance Improvement in Sugarcane - Kai Zhu; Chan Huang; Thi-Thu Phan; Li-Tao Yang; Bao-Qing Zhang; Yong-Xiu Xing; Yang-Rui Li (Plant Molecular Biology Reporter, 2021)

A fungal sirtuin modulates development and virulence in the insect pathogen, Beauveria bassiana - Qing Cai; Li Tian; Jia‐Tao Xie; Qiu‐Ying Huang; Ming‐Guang Feng; Nemat O. Keyhani (Environmental Microbiology, 2021)
Summary Chromatin transitions are mediated in part by acetylation/deacetylation post‐translational modifications of histones. Histone deacetylases, e.g. sirtuins (Sir‐proteins), repress transcription via promotion of heterochromatin formation. Here, we characterize the Sir2 class III histone deacetylase ( BbSir2 ) in the environmentally and economically important fungal insect pathogen, Beauveria bassiana . BbSir2 is shown to contribute to the deacetylation of lysine residues on H3 and H4 histones. Targeted gene knockout of BbSir2 resulted in impaired asexual development, reduced abilities to utilize various carbon/nitrogen sources, reduced tolerance to oxidative, heat, and UV stress, and attenuated virulence. ΔBbSir2 cells showed disrupted cell cycle development and abnormal hyphal septation patterns. Proteomic protein acetylation analyses of wild type and ΔBbSir2 cells revealed the differential abundance of 462 proteins and altered (hyper‐ or hypo‐) acetylation of 436 lysine residues on 350 proteins. Bioinformatic analyses revealed enrichment in pathways involved in carbon/nitrogen metabolism, cell cycle control and cell rescue, defence and mitochondrial functioning. Critical targets involved in virulence included LysM effector proteins and a benzoquinone oxidoreductase implicated in detoxification of cuticular compounds. These data indicate broad effects of BbSir2 on fungal development and stress response, with identification of discrete targets that can account for the observed (decreased) virulence phenotype.

Quartz grain surface microtextural evidence for provenance of the Quaternary aggradation red earth deposit, southern China - Qing-bin Fan; Jie Liao; Li Yan; Wei Ye; Tao Wang; Xiao Feng (Journal of Mountain Science, 2021)

Effects of drought and heat on the productivity and photosynthetic characteristics of alpine meadow plants on the Qinghai-Tibetan Plateau - Li Ma; Zhong-hua Zhang; Bu-qing Yao; Zhen Ma; Xiao-tao Huang; Bing-rong Zhou; Man-hou Xu; Jing Guo; Hua-kun Zhou (Journal of Mountain Science, 2021)

Trade-offs/Synergies in Land-use Function Changes in Central China from 2000 to 2015 - Qing Li; Yong Zhou; Tao Xu; Li Wang; Qian Zuo; Jingyi Liu; Xueping Su; Nan He; Zhengxiang Wu (Chinese Geographical Science, 2021)

Short-term waterlogging-induced autophagy in root cells of wheat can inhibit programmed cell death - Li-Lang Zhou; Kai-Yue Gao; Li-Sha Cheng; Yue-Li Wang; Yi-Keng Cheng; Qiu-Tao Xu; Xiang-Yi Deng; Ji-Wei Li; Fang-Zhu Mei; Zhu-Qing Zhou (Protoplasma, 2021)

Using the Metabolome to Understand the Mechanisms Linking Chronic Arsenic Exposure to Microglia Activation, and Learning and Memory Impairment - Rui-Yuan Zhang; Jie-Bai Tu; Rui-Tu Ran; Wen-Xuan Zhang; Qiang Tan; Ping Tang; Tao Kuang; Shu-Qun Cheng; Cheng-Zhi Chen; Xue-Jun Jiang; Chang Chen; Ting-Li Han; et al. (Neurotoxicity Research, 2021)

OsGSTU6 Contributes to Cadmium Stress Tolerance in Rice by Involving in Intracellular ROS Homeostasis - Xiu-Qing Jing; Meng-Ru Zhou; Xiu-Min Nie; Lu Zhang; Peng-Tao Shi; Abdullah Shalmani; Hai Miao; Wen-Qiang Li; Wen-Ting Liu; Kun-Ming Chen (Journal of Plant Growth Regulation, 2021)

Identification of a novel pepper-infecting monopartite begomovirus in China - Pengbai Li; Tao Ruan; Qiyuan Meng; Ke Li; Ling Qing (Archives of Virology, 2021)

Correction to: Utilization of a Wheat55K SNP array-derived high-density genetic map for high-resolution mapping of quantitative trait loci for important kernel-related traits in common wheat - Tianheng Ren; Tao Fan; Shulin Chen; Chunsheng Li; Yongyan Chen; Xia Ou; Qing Jiang; Zhenglong Ren; Feiquan Tan; Peigao Luo; Chen Chen; Zhi Li (Theoretical and Applied Genetics, 2021)

Identification of miRNA targets in eggplant in response to Verticillium dahliae by degradome sequencing - Ting Li; Nianjiao Tao; Yuanmi Lin; Min Chen; Dongli Jiao; Chunmei Xue; Wenjiao Zhu; Qing Yang (European Journal of Plant Pathology, 2021)

Utilization of a Wheat55K SNP array-derived high-density genetic map for high-resolution mapping of quantitative trait loci for important kernel-related traits in common wheat - Tianheng Ren; Tao Fan; Shulin Chen; Chunsheng Li; Yongyan Chen; Xia Ou; Qing Jiang; Zhenglong Ren; Feiquan Tan; Peigao Luo; Chen Chen; Zhi Li (Theoretical and Applied Genetics, 2021)

Phosphorylation at S548 as a Functional Switch of Sterile Alpha and TIR Motif-Containing 1 in Cerebral Ischemia/Reperfusion Injury in Rats - Tao Xue; Qing Sun; Yijie Zhang; Xin Wu; Haitao Shen; Xiang Li; Jiang Wu; Haiying Li; Zhong Wang; Gang Chen (Molecular Neurobiology, 2021)

TRIP13 promotes the proliferation and invasion of lung cancer cells via the Wnt signaling pathway and epithelial–mesenchymal transition - Zhi-Han Li; Lei Lei; Liang-Ru Fei; Wen-Jing Huang; Yi-Wen Zheng; Mai-Qing Yang; Zhao Wang; Chen-Chen Liu; Hong-Tao Xu (Journal of Molecular Histology, 2021)

7,8-Dihydroxyflavone Alleviates Anxiety-Like Behavior Induced by Chronic Alcohol Exposure in Mice Involving Tropomyosin-Related Kinase B in the Amygdala - Na Wang; Xing Liu; Xin-Tong Li; Xin-Xin Li; Wei Ma; Yan-Min Xu; Yong Liu; Qing Gao; Tao Yang; Hongxuan Wang; Ying Peng; Xiao-Feng Zhu; et al. (Molecular Neurobiology, 2021)

Late Pennsylvanian carbonate platform facies and coral reef: new insights from southern China (Guizhou Province) - Marine Maillet; Wen-Tao Huang; Xiao Li; Zhen-Yuan Yang; Chang-Qing Guan; Yong-Li Zhang; En-Pu Gong; Katsumi Ueno; Elias Samankassou (Facies, 2021)
The Pennsylvanian is characterized by intense paleoenvironmental changes related to glacio-eustatic sea-level fluctuations and major tectonic events, which affected the evolution of biocommunities. Most known Pennsylvanian tropical reefs and mounds are predominantly composed of calcareous algae (e.g. phylloid algae, Archaeolithophyllum ), calcareous sponges, fenestrate bryozoans, Tubiphytes , and microbialites. However, in Houchang (southern China), the Late Pennsylvanian carbonate platform records a large coral reef lacking any analogs in age (Gzhelian), size (80–100 m thick) and composition (high biodiversity). The large coral reef developed at the border of the Luodian intraplatform basin. The intraplatform basin is characterized by the deposition of green algal grainstone, coated grain grainstone and bioclastic packstone, grainstone, floatstone and rudstone in shallow-waters. In the deep-water shelf, lithofacies are composed of burrowed bioclastic wackestone, microbioclastic peloidal packstone, grainstone, and fine-grained burrowed wackestone and packstone. In this context, the coral reef developed on a deep-shelf margin, in a moderate to low energy depositional environment, below the FWWB. The scarcity of Pennsylvanian coral reefs suggests global unfavorable conditions, which can be attributed to a complex pattern of several environmental factors, including seawater chemistry (aragonite seas), paleoclimatic cooling related to continental glaciation, and the biological competition with the more opportunistic and adaptive phylloid algal community that occupied similar platform margin paleoenvironments. The existence of the large Bianping coral reef in southern China, as well as a few additional examples of Pennsylvanian coralliferous bioconstructions, provides evidence that coral communities were able to endure the Late Paleozoic fluctuating paleoenvironmental conditions in specific settings. One of such settings appears to have been the deep shelf margin, where low light levels decreased competition with the phylloid algal community.

A novel high-performance CeO2-CuMn2O4 catalyst for toluene degradation - Ting Zhou; Aijuan Xie; Qing Wang; Xiang Li; Zerui Zhu; Wanqi Zhang; Yuwei Tao; Shiping Luo (Environmental Science and Pollution Research, 2020)

Prevalence and Bayesian Phylogenetics of Enteroviruses Derived From Environmental Surveillance Around Polio Vaccine Switch Period in Shandong Province, China - Chenxu Zhao; Xiaojuan Lin; Feng Ji; Ping Xiong; Yao Liu; Suting Wang; Peng Chen; Qing Xu; Li Zhang; Zexin Tao; Aiqiang Xu (Food and Environmental Virology, 2020)

Recent rainfall- and excavation-induced bedding rockslide occurring on 22 October 2018 along the Jian-En expressway, Hubei, China - Haibing Yu; Changdong Li; Jia-Qing Zhou; Wenqiang Chen; Jingjing Long; Xutao Wang; Tao Peng (Landslides, 2020)

Aluminum and magnesium status during pregnancy and placenta oxidative stress and inflammatory mRNA expression: China Ma’anshan birth cohort study - Jian-Qing Wang; Ya-Bin Hu; Chun-Mei Liang; Xun Xia; Zhi-Juan Li; Hui Gao; Jie Sheng; Kun Huang; Su-Fang Wang; Yan Li; Peng Zhu; Jia-Hu Hao; et al. (Environmental Geochemistry and Health, 2020)

Assessing major factors impacts on the hydrogeochemistry in a riverside alluvial aquifer, northeast China - Li Wang; Tao Du; Qing Hu; Sijie Lin; Mingzhu Liu; Honghan Chen (Arabian Journal of Geosciences, 2020)

CsNPF7.2 Has a Potential to Regulate Cucumber Seedling Growth in Early Nitrogen Deficiency Stress - Xi Hu; Jiali Zhang; Wenqian Liu; Qing Wang; Tao Wang; Xiaojun Li; Xiaohong Lu; Lihong Gao; Wenna Zhang (Plant Molecular Biology Reporter, 2020)

Mitochondrial Transplantation Attenuates Brain Dysfunction in Sepsis by Driving Microglial M2 Polarization - Chaoying Yan; Zhi Ma; Hongli Ma; Qing Li; Qian Zhai; Tao Jiang; Zhanqin Zhang; Qiang Wang (Molecular Neurobiology, 2020)

Molecular Characterization and Promoter Analysis of Novel Sugar Transporter Gene ScERD6 in Sugarcane - Xiao-Rong Miao; Xu-Peng Zeng; Jun-Qi Niu; Aamir Mahmood; Li-Tao Yang; Bao-Qing Zhang; Yang-Rui Li (Sugar Tech, 2020)

Chopper Sugarcane Combine Harvester with Middle-Mounted Primary Extractor - Tao Wu; Xiao-Ling Liang; Qing-Ting Liu; Zeng-Xue Zhang; Hai Xu; Ji-Bai Huang; Jin-Xin Li; Xiao-Ping Zou (Sugar Tech, 2020)

Summer albedo variations in the Arctic Sea ice region from 1982 to 2015 - Hai‐Tao Peng; Chang‐Qing Ke; Xiaoyi Shen; Mengmeng Li; Zhu‐De Shao (International Journal of Climatology, 2020)
The spatiotemporal changes in the sea ice region albedo over the entire Arctic region and in eight subregions (the Central Arctic Ocean [CAO], the Beaufort and Chukchi Seas [BC], the East Siberian and Laptev Seas [ESL], Baffin Bay and Labrador Sea [BL], the Canadian Archipelago [CA], the Greenland Sea [GS], Hudson Bay [HB] and the Kara and Barents Seas [KB]) in the summer of 1982–2015 are analysed with CLARA‐A2‐SAL data. The results indicate that in the summer of 1982–2015, the Arctic Sea ice region albedo fluctuated with a downward trend of −1.6% per decade (significance level of 99%). The BC had the largest decline in the albedo trend of −2.7% per decade (significance level of 99%), and most other subregions had downward trends except the GS, which exhibited a slight upward trend. The mean Arctic Sea ice region albedo was 44%. The high albedo areas were mainly concentrated in the CAO and the vicinity of Greenland. The albedo decreased with decreasing latitude, while the low‐value areas were mainly concentrated in the outer sea ice area. In the Arctic region, both the sea ice concentration (SIC) and the sea ice extent (SIE) showed a decreasing trend, while the near‐surface air temperature (NSAT) and the summer Central Arctic Index (CAI) showed an increasing trend. The Arctic Sea ice region albedo was positively correlated with the SIC and the SIE (0.84, 0.78) and negatively correlated with the NSAT (−0.72), all with a statistical significance level of 99%. The correlation between sea ice region albedo and the summer CAI revealed different relationships in these regions. The BC and ESL had a significant negative correlation, and the GS showed a significant positive correlation. These findings indicated that the decrease in albedo is closely related to the reduction in Arctic Sea ice and the increase in air temperature. In addition, the sea ice region albedo variations in the BC, ESL and GS are also greatly influenced by atmospheric circulation.

Brain-Wide Shape Reconstruction of a Traced Neuron Using the Convex Image Segmentation Method - Shiwei Li; Tingwei Quan; Hang Zhou; Qing Huang; Tao Guan; Yijun Chen; Cheng Xu; Hongtao Kang; Anan Li; Ling Fu; Qingming Luo; Hui Gong; et al. (Neuroinformatics, 2020)

Chloroplast genome of an extremely endangered conifer Thuja sutchuenensis Franch.: gene organization, comparative and phylogenetic analysis - Tao Yu; Bing-Hong Huang; Yuyang Zhang; Pei-Chun Liao; Jun-Qing Li (Physiology and Molecular Biology of Plants, 2020)

Primary age-related tauopathy in a Chinese cohort - Xin Wang; Lei Zhang; Hui Lu; Juan-li Wu; Hua-zheng Liang; Chong Liu; Qing-qing Tao; Zhi-ying Wu; Ke-qing Zhu (Journal of Zhejiang University-SCIENCE B, 2020)

Genome-Wide Identification of Malectin/Malectin-Like Domain Containing Protein Family Genes in Rice and Their Expression Regulation Under Various Hormones, Abiotic Stresses, and Heavy Metal Treatments - Xiu-Qing Jing; Abdullah Shalmani; Meng-Ru Zhou; Peng-Tao Shi; Izhar Muhammad; Yi Shi; Rahat Sharif; Wen-Qiang Li; Wen-Ting Liu; Kun-Ming Chen (Journal of Plant Growth Regulation, 2020)

Mapping landslide susceptibility at the Three Gorges Reservoir, China, using gradient boosting decision tree, random forest and information value models - Tao Chen; Li Zhu; Rui-qing Niu; C John Trinder; Ling Peng; Tao Lei (Journal of Mountain Science, 2020)

Phylogeography and population dynamics of an endemic oak (Quercus fabri Hance) in subtropical China revealed by molecular data and ecological niche modeling - Xiao-Dan Chen; Jia Yang; Li Feng; Tao Zhou; Hao Zhang; Hui-Min Li; Guo-Qing Bai; Xu Meng; Zhong-Hu Li; Gui-Fang Zhao (Tree Genetics & Genomes, 2020)

The Arabidopsis kinase-associated protein phosphatase KAPP, interacting with protein kinases SnRK2.2/2.3/2.6, negatively regulates abscisic acid signaling - Kai Lu; Ya-Dong Zhang; Chun-Fang Zhao; Li-Hui Zhou; Qing-Yong Zhao; Tao Chen; Cai-Lin Wang (Plant Molecular Biology, 2020)

Direct Z-scheme La1-xCexMnO3 catalyst for photothermal degradation of toluene - Yiran Tang; Yuwei Tao; Ting Zhou; Baozhu Yang; Qing Wang; Zerui Zhu; Aijuan Xie; Shiping Luo; Chao Yao; Xiazhang Li (Environmental Science and Pollution Research, 2019)

Genetic Association Between NGFR, ADAM17 Gene Polymorphism, and Parkinson’s Disease in the Chinese Han Population - Wei-Wei Li; Ying-Ying Shen; Dong-Wan Chen; Hui-Yun Li; Qian-Qian Shi; Jing Mei; Heng Yang; Fa-Ying Zhou; An-Yu Shi; Tao Zhang; Xiu-Qing Yao; Zhi-Qiang Xu; et al. (Neurotoxicity Research, 2019)

Fn14 Participates in Neuropathic Pain Through NF-κB Pathway in Primary Sensory Neurons - Li-Na Huang; Yun Zou; Shao-Gen Wu; Hong-Hong Zhang; Qing-Xiang Mao; Jin-Bao Li; Yuan-Xiang Tao (Molecular Neurobiology, 2019)

An MAP kinase interacts with LHK1 and regulates nodule organogenesis in Lotus japonicus - Jun Yin; Xiaomin Guan; Heng Zhang; Longxiang Wang; Hao Li; Qing Zhang; Tao Chen; Zeyuan Xu; Zonglie Hong; Yangrong Cao; Zhongming Zhang (Science China Life Sciences, 2019)

Cytotoxic abietane and kaurane diterpenoids from Celastrus orbiculatus - Wei Jiang; Ti-Zhuang Shan; Jia-Jun Xu; Wen-Ju Chen; Li Miao; Meng-Ying Lv; Li Tao; Yan-Qing Liu (Journal of Natural Medicines, 2019)

The Serum BDNF Level Offers Minimum Predictive Value for Motor Function Recovery After Stroke - Wenshu Luo; Tao Liu; Shanshan Li; Hongmei Wen; Fenghua Zhou; Ross Zafonte; Xun Luo; Minghzu Xu; Randie Black-Schaffer; Lisa J. Wood; Yulong Wang; Qing Mei Wang (Translational Stroke Research, 2019)

Molecular Cloning and Expression Analysis of ScTUA Gene in Sugarcane - Bao-Qing Zhang; Min Shao; Yong-Jian Liang; Xing Huang; Xiu-Peng Song; Hu Chen; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2019)

Seldom-segment versus multi-segment intramedullary spinal cord gliomas: a comparative clinical study - Jianjun Sun; Zhenyu Wang; Zhendong Li; Haibo Wu; Mei Zheng; Qing Chang; Yunfeng Han; Zhihui Cui; Hung I. Liao; Tao Wang; Xiaodong Chen; Xuan Yang; et al. (Science China Life Sciences, 2019)

Effects of periodical drying and non-drying on nutrient content and desiccation tolerance of an intertidal Pyropia yezoensis strain subject to farming conditions - Wen Jun Wang; Xiao Lei Li; Teng Qing Sun; Zhou Rui Liang; Fu Li Liu; Xiu Tao Sun; Fei Jiu Wang (Journal of Applied Phycology, 2019)

Benzopyran derivatives from endophytic Daldinia eschscholzii JC-15 in Dendrobium chrysotoxum and their bioactivities - Ming Hu; Xue-Qiong Yang; Qing-Yan Zhou; Shu-Quan Li; Bang-Yan Wang; Bao-Hui Ruan; Ya-Bin Yang; Zhuo-Xi Zhang; Hao Zhou; Zhong-Tao Ding (Natural Product Research, 2019)

Influences of soil moisture and salt content on loess shear strength in the Xining Basin, northeastern Qinghai-Tibet Plateau - Jiang-tao Fu; Xia-song Hu; Xi-lai Li; Dong-mei Yu; Ya-bin Liu; You-Qing Yang; Zhao-xin Qi; Shu-xia Li (Journal of Mountain Science, 2019)

Study on Surrounding Rock Stability of Small Clear-Distance Twin Highway Tunnel with Eight Lanes - Qing Jiang; Shu-guang Song; Tao Li; Kang Wang; Rui-hai Gu (Geotechnical and Geological Engineering, 2019)

The research progress in mechanism and influence of biosorption between lactic acid bacteria and Pb(II): A review - Derong Lin; Ran Ji; Dan Wang; Mengshi Xiao; Jingjing Zhao; Jinpeng Zou; Yutong Li; Tao Qin; Baoshan Xing; Yuan Chen; Peng Liu; Zhijun Wu; et al. (Critical Reviews in Food Science and Nutrition, 2019)

The relative strength of different floral visitors driving floral evolution within a Primula secundiflora population - Yun Wu; Tao Zhong; Guang-Li Liu; Lu-Wei Tan; Qing-Jun Li (Evolutionary Ecology, 2018)

Lycium barbarum polysaccharide attenuates diabetic testicular dysfunction via inhibition of the PI3K/Akt pathway-mediated abnormal autophagy in male mice - Guang-Jiang Shi; Jie Zheng; Xiao-Xu Han; Ya-Ping Jiang; Zhi-Mei Li; Jing Wu; Qing Chang; Yang Niu; Tao Sun; Yu-Xiang Li; Zhen Chen; Jian-Qiang Yu (Cell and Tissue Research, 2018)

The mitochondrial genome of the Kentish Plover Charadrius alexandrinus (Charadriiformes: Charadriidae) and phylogenetic analysis of Charadrii - Wan Chen; Chenling Zhang; Tao Pan; Wei Liu; Kexin Li; Chaochao Hu; Qing Chang (Genes & Genomics, 2018)

A comparison of CRISPR/Cas9 and siRNA-mediated ALDH2 gene silencing in human cell lines - Fei Wang; Tao Guo; Hongmei Jiang; Ruobi Li; Ting Wang; Ni Zeng; Guanghui Dong; Xiaowen Zeng; Daochuan Li; Yongmei Xiao; Qiansheng Hu; Wen Chen; et al. (Molecular Genetics and Genomics, 2018)

Fast local wavenumber (FLW) method for the inversion of magnetic source parameters - Guo-Qing Ma; Yan-Bo Ming; Jiang-Tao Han; Li-Li Li; Qing-Fa Meng (Applied Geophysics, 2018)

Cotton (Gossypium hirsutum) JAZ3 and SLR1 function in jasmonate and gibberellin mediated epidermal cell differentiation and elongation - Xiao-Cong Xia; Qian-Qian Hu; Wen Li; Yun Chen; Li-Hong Han; Miao Tao; Wen-Ying Wu; Xue-Bao Li; Geng-Qing Huang (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

The key gluconeogenic gene PCK1 is crucial for virulence of Botrytis cinerea via initiating its conidial germination and host penetration - Jian‐Kang Liu; Hao‐Wu Chang; Yue Liu; Yu (Haity) Qin; Yu‐Han Ding; Lan Wang; Yue Zhao; Ming‐Zhe Zhang; Sheng‐Nan Cao; Le‐Tao Li; Wei Liu; Gui‐Hua Li; et al. (Environmental Microbiology, 2018)
Summary The process of initiation of host invasion and survival of some foliar phytopathogenic fungi in the absence of external nutrients on host leaf surfaces remains obscure. Here, we demonstrate that gluconeogenesis plays an important role in the process and nutrient‐starvation adaptation before the pathogen host invasion. Deletion of phosphoenolpyruvate c arboxy k inase gene BcPCK1 in gluconeogenesis in Botrytis cinerea , the causative agent of grey mould, resulted in the failure of the Δ Bcpck1 mutant conidia to germinate on hard and hydrophobic surface and penetrate host cells in the absence of glucose, reduction in conidiation and slow conidium germination in a nutrient‐rich medium. The wild‐type and Δ Bcpck1 conidia germinate similarly in the presence of glucose (higher concentration) as the sole carbon source. Conidial glucose‐content should reach a threshold level to initiate germination and host penetration. Infection structure formation by the mutants displayed a glucose‐dependent fashion, which corresponded to the mutant virulence reduction. Exogenous glucose or complementation of BcPCK1 completely rescued all the developmental and virulence defects of the mutants. Our findings demonstrate that BcPCK1 plays a crucial role in B. cinerea pathogenic growth and virulence, and provide new insights into gluconeogenesis mediating pathogenesis of plant fungal pathogens via initiation of conidial germination and host penetration.

Periodical drying or no drying during aquaculture affects the desiccation tolerance of a sublittoral Pyropia yezoensis strain - Xiao-lei Li; Wen-jun Wang; Fu-li Liu; Zhou-rui Liang; Xiu-tao Sun; Hai-qing Yao; Fei-jiu Wang (Journal of Applied Phycology, 2018)

Two alphapartitiviruses co-infecting a single isolate of the plant pathogenic fungus Rhizoctonia solani - Ruiling Lyu; Yi Zhang; Qing Tang; Yangyi Li; Jiasen Cheng; Yanping Fu; Tao Chen; Daohong Jiang; Jiatao Xie (Archives of Virology, 2018)

Phylogenetic and genetic characterization of a 2017 clinical isolate of H7N9 virus in Guangzhou, China during the fifth epidemic wave - Yongqiang Deng; Chunlin Li; Jianfeng Han; Yingfen Wen; Jian Wang; Wenxing Hong; Xiaofeng Li; Zhongyu Liu; Qing Ye; Jing Li; Changshuai Zhou; Lei Yu; et al. (Science China Life Sciences, 2017)

Cloning and characterization of Agp1, the gene encoding the small subunit of ADP-glucose pyrophosphorylase from wheat and its relatives - Xiao-Wei Zhang; Qing Wang; Ling-Ling Zhang; Xiao-Juan Zhong; Qian-Tao Jiang; Jian Ma; Peng-Fei Qi; Wei Li; Guo-Yue Chen; Xiu-Jin Lan; Mei Deng; Zhen-Xiang Lu; et al. (Biologia, 2017)

The Influence of Temperature on Mode I Fracture Toughness and Fracture Characteristics of Sandstone - Gan Feng; Yong Kang; Tao Meng; Yao-qing Hu; Xiao-hong Li (Rock Mechanics and Rock Engineering, 2017)

Early-Life Social Isolation-Induced Depressive-Like Behavior in Rats Results in Microglial Activation and Neuronal Histone Methylation that Are Mitigated by Minocycline - Hong-Tao Wang; Fu-Lian Huang; Zhao-Lan Hu; Wen-Juan Zhang; Xiao-Qing Qiao; Yan-Qing Huang; Ru-Ping Dai; Fang Li; Chang-Qi Li (Neurotoxicity Research, 2017)

Genetic Variants of Microtubule Actin Cross-linking Factor 1 (MACF1) Confer Risk for Parkinson’s Disease - Xin Wang; Nuomin Li; Nian Xiong; Qi You; Jie Li; Jinlong Yu; Hong Qing; Tao Wang; Heather J. Cordell; Ole Isacson; Jeffery M. Vance; Eden R. Martin; et al. (Molecular Neurobiology, 2017)

Associations Between Hepatic Functions and Plasma Amyloid-Beta Levels—Implications for the Capacity of Liver in Peripheral Amyloid-Beta Clearance - Ye-Ran Wang; Qing-Hua Wang; Tao Zhang; Yu-Hui Liu; Xiu-Qing Yao; Fan Zeng; Jing Li; Fa-Yin Zhou; Lin Wang; Jia-Chuan Yan; Hua-Dong Zhou; Yan-Jiang Wang (Molecular Neurobiology, 2017)

Description of a new Neoactinomyxum type actinosporean from the oligochaete Branchiura sowerbyi Beddard - Bing Wen Xi; Peng Li; Qing Chun Liu; Kai Chen; Tao Teng; Jun Xie (Systematic Parasitology, 2017)

Erratum to: Chryseobacterium zhengzhouense sp. nov., isolated from groundwater of a well in a vegetable field - Ya-Nan Wang; Wei-Hong He; Ming-Li An; Wen-Yu Tian; Xiao-Yan You; Fang-Qing Ying; Jing Guo; Tao Gong (Antonie van Leeuwenhoek, 2017)

Comparative genomic analysis of isoproturon‐mineralizing sphingomonads reveals the isoproturon catabolic mechanism - Xin Yan; Tao Gu; Zhongquan Yi; Junwei Huang; Xiaowei Liu; Ji Zhang; Xihui Xu; Zhihong Xin; Qing Hong; Jian He; Jim C. Spain; Shunpeng Li; et al. (Environmental Microbiology, 2016)
Summary The worldwide use of the phenylurea herbicide, isoproturon (IPU), has resulted in considerable concern about its environmental fate. Although many microbial metabolites of IPU are known and IPU‐mineralizing bacteria have been isolated, the molecular mechanism of IPU catabolism has not been elucidated yet. In this study, complete genes that encode the conserved IPU catabolic pathway were revealed, based on comparative analysis of the genomes of three IPU‐mineralizing sphingomonads and subsequent experimental validation. The complete genes included a novel hydrolase gene ddhA , which is responsible for the cleavage of the urea side chain of the IPU demethylated products; a distinct aniline dioxygenase gene cluster adoQTA1A2BR , which has a broad substrate range; and an inducible catechol meta ‐cleavage pathway gene cluster adoXEGKLIJC . Furthermore, the initial mono‐ N ‐demethylation genes pdmAB were further confirmed to be involved in the successive N ‐demethylation of the IPU mono‐ N ‐demethylated product. These IPU‐catabolic genes were organized into four transcription units and distributed on three plasmids. They were flanked by multiple mobile genetic elements and highly conserved among IPU‐mineralizing sphingomonads. The elucidation of the molecular mechanism of IPU catabolism will enhance our understanding of the microbial mineralization of IPU and provide insights into the evolutionary scenario of the conserved IPU‐catabolic pathway.

Influence of genetic polymorphisms in cytochrome P450 oxidoreductase on the variability in stable warfarin maintenance dose in Han Chinese - Wu-Tao Zeng; Qing Xu; Cheng-Hsun Li; Wei-Yan Chen; Xiu-Ting Sun; Xiang Wang; Yi-Ying Yang; Hui Shi; Zhi-Sheng Yang (European Journal of Clinical Pharmacology, 2016)

An extracellular Zn‐only superoxide dismutase from Puccinia striiformis confers enhanced resistance to host‐derived oxidative stress - Jie Liu; Tao Guan; Peijing Zheng; Liyang Chen; Yang Yang; Baoyu Huai; Dan Li; Qing Chang; Lili Huang; Zhensheng Kang (Environmental Microbiology, 2016)
Summary Accumulation of reactive oxygen species (ROS) following plant‐pathogen interactions can trigger plant defence responses and directly damage pathogens. Thus, it is essential for pathogens to scavenge host‐derived ROS to establish a parasitic relationship. However, the mechanisms protecting pathogens from host‐derived oxidative stress remain unclear. In this study, a superoxide dismutase (SOD) gene, PsSOD1 , was cloned from a wheat— Puccinia striiformis f. sp. tritici ( Pst ) interaction cDNA library. Transcripts of PsSOD1 were up‐regulated in the early infection stage. Heterologous mutant complementation and biochemical characterization revealed that PsSOD1 encoded a Zn‐only SOD. The predicted signal peptide was functional in an invertase‐mutated yeast strain. Furthermore, immunoblot analysis of apoplastic proteins in Pst ‐infected wheat leaves and bimolecular fluorescence complementation suggested that PsSOD1 is a secreted protein that potentially forms a dimer during Pst infection. Overexpression of PsSOD1 enhanced Schizosaccharomyces pombe resistance to exogenous superoxide. Transient expression of PsSOD1 in Nicotiana benthamiana suppressed Bax‐induced cell death. Knockdown of PsSOD1 using a host‐induced gene silencing (HIGS) system reduced the virulence of Pst , which was associated with ROS accumulation in HIGS plants. These results suggest that PsSOD1 is an important pathogenicity factor that is secreted into the host‐pathogen interface to contribute to Pst infection by scavenging host‐derived ROS.

Transcriptome of High-Sucrose Sugarcane Variety GT35 - Dong-Liang Huang; Yi-Jing Gao; Yi-Yun Gui; Zhong-Liang Chen; Cui-Xian Qin; Miao Wang; Qing Liao; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2016)

Chryseobacterium zhengzhouense sp. nov., isolated from groundwater of the well in a vegetable field, and emended description of the genus Chryseobacterium - Ya-Nan Wang; Wei-Hong He; Ming-Li An; Wen-Yu Tian; Xiao-Yan You; Fang-Qing Ying; Jing Guo; Tao Gong (Antonie van Leeuwenhoek, 2016)

Antidepressant-like effects of standardized gypenosides: involvement of brain-derived neurotrophic factor signaling in hippocampus - Rong-Hao Mu; Xiao-Yan Fang; Shuang-Shuang Wang; Cheng-Fu Li; Shao-Mei Chen; Xue-Mei Chen; Qing Liu; Yu-Cheng Li; Li-Tao Yi (Psychopharmacology, 2016)

Association of interleukin-1 family cytokines single nucleotide polymorphisms with susceptibility to systemic sclerosis: an independent case–control study and a meta-analysis - Xiao-Lei Huang; Guo-Cui Wu; Yu-Jie Wang; Xiao-Ke Yang; Guo-Jun Yang; Jin-Hui Tao; Yu Duan; Jun-Wei Yan; Xiang-Pei Li; Dong-Qing Ye; Jing Wang (Immunologic Research, 2016)

Paraventricular Nucleus Infusion of Epigallocatechin-3-O-Gallate Improves Renovascular Hypertension - Qiu-Yue Yi; Jie Qi; Xiao-Jing Yu; Hong-Bao Li; Yan Zhang; Qing Su; Tao Shi; Dong-Mei Zhang; Jing Guo; Zhi-Peng Feng; Mo-Lin Wang; Guo-Qing Zhu; et al. (Cardiovascular Toxicology, 2016)

QTL mapping of dehiscence length at the basal part of thecae related to heat tolerance of rice (Oryza sativa L.) - Ling Zhao; Chun-Fang Zhao; Li-Hui Zhou; Jing Lin; Qing-Yong Zhao; Zhen Zhu; Tao Chen; Shu Yao; Toshihiro Hasegawa; Tsutomu Matsui; Cai-Lin Wang (Euphytica, 2016)

Hsp27 gene in Drosophila ananassae subgroup was split by a recently acquired intron - LI ZHANG; HAN KANG; SHAN JIN; QING TAO ZENG; YONG YANG (Journal of Genetics, 2016)

Isolation, identification and genomic characterization of the Asian lineage Zika virus imported to China - Yong-Qiang Deng; Hui Zhao; Xiao-Feng Li; Na-Na Zhang; Zhong-Yu Liu; Tao Jiang; Da-Yong Gu; Lei Shi; Jian-An He; Hong-Jiang Wang; Zhao-Zeng Sun; Qing Ye; et al. (Science China Life Sciences, 2016)

Mechanism Underlying the Analgesic Effect Exerted by Endomorphin-1 in the rat Ventrolateral Periaqueductal Gray - Tao Chen; Jing Li; Ban Feng; Rui Hui; Yu-Lin Dong; Fu-Quan Huo; Ting Zhang; Jun-Bin Yin; Jian-Qing Du; Yun-Qing Li (Molecular Neurobiology, 2016)

Removal of fluorescent dissolved organic matter in biologically treated textile effluents by NDMP anion exchange process: efficiency and mechanism - Wen-Tao Li; Zi-Xiao Xu; Chen-Dong Shuang; Qing Zhou; Hai-Bo Li; Ai-Min Li (Environmental Science and Pollution Research, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

The Tau-Induced Reduction of mRNA Levels of Kv Channels in Human Neuroblastoma SK-N-SH Cells - Xi-Mu Hu; Xiao-Qing Li; Xian-Tao Li (Journal of Molecular Neuroscience, 2016)

Circadian variations in behaviors, BDNF and cell proliferation in depressive mice - Li-Tao Yi; Liu Luo; Yong-Jing Wu; Bin-Bin Liu; Xiao-Long Liu; Di Geng; Qing Liu (Metabolic Brain Disease, 2015)

Soil labile organic carbon fractions in rhizosphere soil in citrus plantations in the Three Gorges Reservoir Area - Guo-Mei Jia; Bao-Lin Zhang; Jun-Tao Niu; Li-Ming Wang; Fang-Qing Chen (Agroforestry Systems, 2015)

Tetrodotoxin detection and species identification of pufferfish in retail roasted fish fillet by DNA barcoding in China - Nan Li; Qing Shen; Jiahui Wang; Chunhui Han; Rong Ji; Fengqin Li; Tao Jiang (Food Additives & Contaminants: Part A, 2015)

Identification of Genes Involved in the Biosynthesis of Tripterygium wilfordii Hook.f. Secondary Metabolites by Suppression Subtractive Hybridization - Guo-peng Miao; Wei Li; Bin Zhang; Zhan-feng Zhang; Zhi-qing Ma; Jun-tao Feng; Xing Zhang; Chuan-shu Zhu (Plant Molecular Biology Reporter, 2015)

NMDAR-Mediated Hippocampal Neuronal Death is Exacerbated by Activities of ASIC1a - Su Gao; Yang Yu; Zhi-Yuan Ma; Hui Sun; Yong-Li Zhang; Xing-Tao Wang; Chaoyun Wang; Wei-Ming Fan; Qing-Yin Zheng; Chun-Lei Ma (Neurotoxicity Research, 2015)

Numerical simulation on slope stability analysis considering anisotropic properties of layered fractured rocks: a case study - Tian-hong Yang; Wen-hao Shi; Pei-tao Wang; Hong-lei Liu; Qing-lei Yu; Yang Li (Arabian Journal of Geosciences, 2015)

Diversity and space–time dynamics of endophytic archaea from sugar beet in the north slope of Tianshan Mountain revealed by 454 pyrosequencing and T-RFLP - YingWu Shi; MuSi TaPa; Chun Li; HongMei Yang; Tao Zhang; Yan Gao; Jian Sun; Jun Zeng; Qing Lin; ZhenHua Cao; KuEr OuTi; YuGuo Li; et al. (World Journal of Microbiology and Biotechnology, 2015)

Radical Gastrectomy Combined with Modified Gastric Bypass Surgery for Gastric Cancer Patients with Type 2 Diabetes - Tao Liu; Guang-wei Xie; Qing-zhong Tian; Jin Li (Cell Biochemistry and Biophysics, 2015)

ACE2 and Ang-(1–7) protect endothelial cell function and prevent early atherosclerosis by inhibiting inflammatory response - Yue-Hui Zhang; Yong-huan Zhang; Xue-Fei Dong; Qing-Qing Hao; Xiao-Ming Zhou; Qing-Tao Yu; Shu-Ying Li; Xu Chen; Abdulai Fallah Tengbeh; Bo Dong; Yun Zhang (Inflammation Research, 2015)

Physiological and Biochemical Characteristics Related to Cold Resistance in Sugarcane - Bao-Qing Zhang; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2015)

Host-Choice Behavior of Diaphorina citri Kuwayama (Hemiptera: Psyllidae) Under Laboratory Conditions - Chuan-Qing Ruan; David G. Hall; Bo Liu; Yong-Ping Duan; Tao Li; Han-Qing Hu; Guo-Cheng Fan (Journal of Insect Behavior, 2015)

Bioaccessibility and health risk of heavy metals in ash from the incineration of different e-waste residues - Xiao-Qing Tao; Dong-Sheng Shen; Jia-Li Shentu; Yu-Yang Long; Yi-Jian Feng; Chen-Chao Shen (Environmental Science and Pollution Research, 2015)

Epidemical features of HAdV-3 and HAdV-7 in pediatric pneumonia in Chongqing, China - Ying Wo; Qing-Bin Lu; Dou-Dou Huang; Xiao-Kun Li; Chen-Tao Guo; Hong-Yu Wang; Xiao-Ai Zhang; Wei Liu; Wu-Chun Cao (Archives of Virology, 2015)

7-Chlorokynurenic acid (7-CTKA) produces rapid antidepressant-like effects: through regulating hippocampal microRNA expressions involved in TrkB-ERK/Akt signaling pathways in mice exposed to chronic unpredictable mild stress - Bin-Bin Liu; Liu Luo; Xiao-Long Liu; Di Geng; Qing Liu; Li-Tao Yi (Psychopharmacology, 2015)

Primary succession of soil enzyme activity and heterotrophic microbial communities along the chronosequence of Tianshan Mountains No. 1 Glacier, China - Jun Zeng; Xiao-xia Wang; Kai Lou; Moniruzzaman Khan Eusufzai; Tao Zhang; Qing Lin; Ying-wu Shi; Hong-mei Yang; Zhong-qing Li (Antonie van Leeuwenhoek, 2015)

Isolation and characterization of dengue virus serotype 2 from the large dengue outbreak in Guangdong, China in 2014 - Hui Zhao; LingZhai Zhao; Tao Jiang; XiaoFeng Li; Hang Fan; WenXin Hong; Yu Zhang; Qin Zhu; Qing Ye; YiGang Tong; WuChun Cao; FuChun Zhang; et al. (Science China Life Sciences, 2014)

Accumulation of FLT3+ CD11c+ dendritic cells in psoriatic lesions and the anti-psoriatic effect of a selective FLT3 inhibitor - Heng-Xiu Yan; Wei-Wei Li; Yan Zhang; Xia-Wei Wei; Li-Xin Fu; Guo-Bo Shen; Tao Yin; Xiu-Ying Li; Hua-Shan Shi; Yang Wan; Qing-Yin Zhang; Jiong Li; et al. (Immunologic Research, 2014)

Genetic diversity analysis of yams (Dioscorea spp.) cultivated in China using ISSR and SRAP markers - Zhi Gang Wu; Xiao Xia Li; Xin Chun Lin; Wu Jiang; Zheng Ming Tao; Nitin Mantri; Chuan Yin Fan; Xiao Qing Bao (Genetic Resources and Crop Evolution, 2014)

Improvement of fluorescent chromosome in situ PCR and its application in the phylogeny of the genus Fagopyrum Mill. using nuclear genes of chloroplast origin (cpDNA) - Fen-Long Li; Friedrich J. Zeller; Kai-Feng Huang; Tao-Xiong Shi; Qing-Fu Chen (Plant Systematics and Evolution, 2013)

Effects of waterlogging on amyloplasts and programmed cell death in endosperm cells of Triticum aestivum L. - Hai-Yan Fan; Zhu-Qing Zhou; Chao-Nan Yang; Zhen Jiang; Jin-Tao Li; Xiang-Xu Cheng; Yue-Jing Guo (Protoplasma, 2013)

MicroRNA-21 promotes the proliferation and inhibits apoptosis in Eca109 via activating ERK1/2/MAPK pathway - Fengxia Liu; Shutao Zheng; Tao Liu; Qing Liu; Meng Liang; Xiuling Li; Ilyar Sheyhidin; Xiaomei Lu; Wenya Liu (Molecular and Cellular Biochemistry, 2013)

Up-regulation of Slc39A2(Zip2) mRNA in peripheral blood mononuclear cells from patients with pulmonary tuberculosis - Yan-ting Tao; Qing Huang; Ya-li Jiang; Xiao-lei Wang; Ping Sun; Yuanyuan Tian; Hai-liang Wu; Min Zhang; Si-bo Meng; Yu-shu Wang; Qing Sun; Lian-ying Zhang (Molecular Biology Reports, 2013)

Stereoselective syntheses of functionalized spirocyclopenteneoxindoles via triphenylphosphine-catalyzed [3+2] cycloaddition reactions - Qing-Fa Zhou; Xue-Ping Chu; Fei-Fei Ge; Cheng Li; Tao Lu (Molecular Diversity, 2013)

Lack of association between IL-23R gene polymorphisms and systemic lupus erythematosus in a Chinese population - Gui-Mei Chen; Chen-Chen Feng; Qian-Ling Ye; Juan Wang; Han Cen; Rui Li; Hui Peng; Mo Zhou; Rui-Xue Leng; Yin-Guang Fan; Jin-Hui Tao; Hai-Feng Pan; et al. (Inflammation Research, 2013)

An exploratory analysis of vegetation strategies to reduce shallow landslide activity on loess hillslopes, Northeast Qinghai-Tibet Plateau, China - Xia-song Hu; Gary Brierley; Hai-li Zhu; Guo-rong Li; Jiang-tao Fu; Xiao-qing Mao; Qin-qin Yu; Na Qiao (Journal of Mountain Science, 2013)
Heavy summer rainfall induces significant soil erosion and shallow landslide activity on the loess hillslopes of the Xining Basin at the northeast margin of the Qinghai-Tibet Plateau. This study examines the mechanical effects of five native shrubs that can be used to reduce shallow landslide activity. We measured single root tensile resistance and shear resistance, root anatomical structure and direct shear and triaxial shear for soil without roots and five rootsoil composite systems. Results show that Atriplex canescens (Pursh) Nutt. possessed the strongest roots, followed by Caragana korshinskii Kom., Zygophyllum xanthoxylon (Bunge) Maxim., Nitraria tangutorum Bobr. and Lycium chinense Mill. Single root strength and shear resistance relationships with root diameter are characterized by power or exponential relations, consistent with the Mohr-Coulomb law. Root mechanical strength reflects their anatomical structure, especially the percentage of phloem and xylem cells, and the degree and speed of periderm lignifications. The cohesion force of root-soil composite systems is notably higher than that of soil without roots, with increasing amplitudes of cohesion force for A. canescens , C. korshinskii , Z. xanthoxylon , N. tangutorum and L. chinense of 75.9%, 75.1%, 36.2%, 24.6% and 17.0 % respectively. When subjected to shear forces, the soil without root samples show much greater lateral deformation than the root-soil composite systems, reflecting the restraining effects of roots. Findings from this paper indicate that efforts to reduce shallow landslides in this region by enhancing root reinforcement will be achieved most effectively using A. canescens and C. korshinskii .

Prediction of soil organic matter using artificial neural network and topographic indicators in hilly areas - Peng-Tao Guo; Wei Wu; Qing-Kai Sheng; Mao-Fen Li; Hong-Bin Liu; Zheng-Yin Wang (Nutrient Cycling in Agroecosystems, 2013)

Viral load of HPV 16/18 in esophageal squamous cell carcinoma in three ethnic groups living in Xinjiang Autonomous Region, China - Tao Liu; Qing Liu; Meng Liang; Shutao Zheng; Xiu Ling Li; Xiaomei Lu; Ilyar Sheyhidin (Molecular Biology Reports, 2013)

Domestication and geographic origin of O ryza sativa in C hina: insights from multilocus analysis of nucleotide variation of O . sativa and O . rufipogon - Xin Wei; Wei‐Hua Qiao; You‐Tao Chen; Rong‐Sheng Wang; Li‐Rong Cao; Wan‐Xia Zhang; Nan‐Nan Yuan; Zi‐Chao Li; Han‐Lai Zeng; Qing‐Wen Yang (Molecular Ecology, 2012)
Previous studies have indicated that C hina is one of the domestication centres of A sian cultivated rice ( O ryza sativa ), and common wild rice ( O . rufipogon ) is the progenitor of O . sativa . However, the number of domestication times and the geographic origin of A sian cultivated rice in C hina are still under debate. In this study, 100 accessions of A sian cultivated rice and 111 accessions of common wild rice in C hina were selected to examine the relationship between O . sativa and O . rufipogon and thereby infer the domestication and evolution of O . sativa in C hina through sequence analyses of six gene regions, trn C ‐ycf6 in chloroplast genomes, cox3 in mitochondrial genomes and ITS , E hd1 , W axy , H d1 in nuclear genomes. The results indicated that the two subspecies of O . sativa (indica and japonica) were domesticated independently from different populations of O . rufipogon with gene flow occurring later from japonica to indica; S outhern C hina was the genetic diversity centre of O . rufipogon , and the P earl R iver basin near the T ropic of C ancer was the domestication centre of O . sativa in C hina.

Characterization of a Newly Isolated Highly Effective 3,5,6-Trichloro-2-pyridinol Degrading Strain Cupriavidus pauculus P2 - Li Cao; Hongming Liu; Hao Zhang; Ke Huang; Tao Gu; Haiyan Ni; Qing Hong; Shunpeng Li (Current Microbiology, 2012)

Effects of indole-3-acetic acid and auxin transport inhibitors on the style curvature of three Alpinia species (Zingiberaceae) - Yin-Ling Luo; Ting-Ju Bi; Dong Li; Zhi-Long Su; Chuan Tao; Yan-Jiang Luo; Qing-Jun Li (Acta Physiologiae Plantarum, 2012)

FLZ, synthetic squamosamide cyclic derivative, attenuates memory deficit and pathological changes in mice with experimentally induced aging - Fang Fang; Qing-li Wang; Geng-tao Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

Pathology of urethral fibromuscular system related to parturition-induced stress urinary incontinence and TGF-β1/Smad pathway - Guang-Yong Li; Wan-Shou Cui; Feng Zhou; Zhe-Zhu Gao; Hua Xin; Tao Liu; Wei-Ren Li; Yan-Qing Gong; Guang-Yi Bai; Ying-Lu Guo; Zhong-Cheng Xin (Molecular and Cellular Biochemistry, 2012)

C/EBP-α ameliorates CCl4-induced liver fibrosis in mice through promoting apoptosis of hepatic stellate cells with little apoptotic effect on hepatocytes in vitro and in vivo - Li-Li Tao; Yuan-Yuan Cheng; Di Ding; Shuang Mei; Jia-Wen Xu; Juan Yu; Qi Ou-Yang; Long Deng; Qi Chen; Qing-Quan Li; Zu-De Xu; Xiu-Ping Liu (Apoptosis, 2012)

Isolation and identification of an acetoin high production bacterium that can reverse transform 2,3-butanediol to acetoin at the decline phase of fermentation - Xian Zhang; Tao-wei Yang; Qing Lin; Mei-juan Xu; Hai-feng Xia; Zheng-hong Xu; Hua-zhong Li; Zhi-ming Rao (World Journal of Microbiology and Biotechnology, 2011)

The panorama of physiological responses and gene expression of whole plant of maize inbred line YQ7-96 at the three-leaf stage under water deficit and re-watering - Hai-Feng Lu; Hai-Tao Dong; Chang-Bin Sun; Dong-Jin Qing; Ning Li; Zi-Kai Wu; Zhi-Qiang Wang; You-Zhi Li (Theoretical and Applied Genetics, 2011)

Association of BLK (rs13277113, rs2248932) polymorphism with systemic lupus erythematosus: a meta-analysis - Ye Fan; Jin-Hui Tao; Li-Ping Zhang; Lian-Hong Li; Dong-Qing Ye (Molecular Biology Reports, 2011)

Meta-analysis of TYK2 gene polymorphisms association with susceptibility to autoimmune and inflammatory diseases - Jin-Hui Tao; Yan-Feng Zou; Xiao-Liang Feng; Jing Li; Fang Wang; Fan-Ming Pan; Dong-Qing Ye (Molecular Biology Reports, 2011)

Human amniotic fluid-derived stem cells can differentiate into hepatocyte-like cells in vitro and in vivo - Hui Liu; Da-qing Liu; Bao-wei Li; Li-dong Guan; Zhi-feng Yan; Ya-li Li; Xue-tao Pei; Wen Yue; Min Wang; Yan-ping Lu; Hong-mei Peng; Yang Lv (In Vitro Cellular & Developmental Biology - Animal, 2011)

The difference of glutathione antioxidant system in newly weaned and young mice liver and its involvement in isoline-induced hepatotoxicity - Qing-Ning Liang; Yu-Chen Sheng; Ping Jiang; Li-Li Ji; Yu-Ye Xia; Yang Min; Zheng-Tao Wang (Archives of Toxicology, 2011)

Interleukin-21 as a potential therapeutic target for systemic lupus erythematosus - Jing Li; Hai-Feng Pan; Han Cen; Jing Tian; Yan Ma; Jin-Hui Tao; Dong-Qing Ye (Molecular Biology Reports, 2011)

Assessment of spatial distribution of soil loss over the upper basin of Miyun reservoir in China based on RS and GIS techniques - Tao Chen; Rui-qing Niu; Yi Wang; Ping-xiang Li; Liang-pei Zhang; Bo Du (Environmental Monitoring and Assessment, 2011)

Increased urinary 8-hydroxy-2′-deoxyguanosine levels in workers exposed to di-(2-ethylhexyl) phthalate in a waste plastic recycling site in China - Qian Wang; Li Wang; Xi Chen; Kai Min Rao; Shao You Lu; Sheng Tao Ma; Pu Jiang; Dan Zheng; Shun Qing Xu; Hong Yan Zheng; Jian Shu Wang; Zhi Qiang Yu; et al. (Environmental Science and Pollution Research, 2011)

Diabetes mellitus and increased risk of biliary tract cancer: systematic review and meta-analysis - Hong-Bo Ren; Tao Yu; Chao Liu; Yan-Qing Li (Cancer Causes & Control, 2011)

TWEAK as a target for therapy in systemic lupus erythematosus - Rui-Xue Leng; Hai-Feng Pan; Wei-Zi Qin; Chao Wang; Li-Li Chen; Jin-Hui Tao; Dong-Qing Ye (Molecular Biology Reports, 2011)

Effect of stress on mRNA expression of H+-ATPase in osteoclasts - Zhang Qing Hong; Liu Meng Tao; Liu Li (Molecular and Cellular Biochemistry, 2010)

The efficacy of FMD vaccine reduced non-structural proteins with a mAb against 3B protein - Dong Li; Zai-Xin Liu; Pu Sun; Yong-Liang Li; Zeng-Jun Lu; Mei-Na Tian; Ying-Li Chen; Bao-Xia Xie; Hui-Fang Bao; Yuan-Fang Fu; Yi-Mei Cao; Ping-Hua Li; et al. (Veterinary Research Communications, 2010)

TIM-3 as a new therapeutic target in systemic lupus erythematosus - Hai-Feng Pan; Ning Zhang; Wen-Xian Li; Jin-Hui Tao; Dong-Qing Ye (Molecular Biology Reports, 2010)

Cardioprotective effects of anesthetic preconditioning in rats with ischemia-reperfusion injury: propofol versus isoflurane - Xing Tao; Ling-qiao Lu; Qing Xu; Shu-ren Li; Mao-tsun Lin (Journal of Zhejiang University-SCIENCE B, 2009)

Molecular cytogenetic characterization of wheat–Secale africanum amphiploids and derived introgression lines with stripe rust resistance - Zu-Jun Yang; Guang-Rong Li; Ju-Qing Jia; Xue Zeng; Meng-Ping Lei; Zi-Xian Zeng; Tao Zhang; Zheng-Long Ren (Euphytica, 2009)

Transformation of sugarcane with ACC oxidase antisense gene - Ai-Qin Wang; Wei-Qing Dong; Yuan-Wen Wei; Cheng-Mei Huang; Long-Fei He; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2009)

Identification of α-gliadin genes in Dasypyrum in relation to evolution and breeding - Guang-Rong Li; Cheng Liu; Zi-Xian Zeng; Ju-Qing Jia; Tao Zhang; Jian-Ping Zhou; Zheng-Long Ren; Zu-Jun Yang (Euphytica, 2009)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Transplantation of NGF-Gene-Modified Bone Marrow Stromal Cells into a Rat Model of Alzheimer’ Disease - Li-Yan Li; Jin-Tao Li; Qing-Ying Wu; Jin Li; Zhong-Tang Feng; Su Liu; Ting-Hua Wang (Journal of Molecular Neuroscience, 2008)

Transplantation of NGF-Gene-Modified Bone Marrow Stromal Cells into a Rat Model of Alzheimer’ Disease - Li-Yan Li; Jin-Tao Li; Qing-Ying Wu; Jin Li; Zhong-Tang Feng; Su Liu; Ting-Hua Wang (Journal of Molecular Neuroscience, 2008)

Proteomic identification of differently expressed proteins responsible for osteoblast differentiation from human mesenchymal stem cells - Ai-Xia Zhang; Wei-Hua Yu; Bao-Feng Ma; Xin-Bing Yu; Frank Fuxiang Mao; Wei Liu; Jia-Qing Zhang; Xiu-Ming Zhang; Shu-Nong Li; Ming-Tao Li; Bruce T. Lahn; Andy Peng Xiang (Molecular and Cellular Biochemistry, 2007)

Cellular and molecular responses in progressive pseudorheumatoid dysplasia articular cartilage associated with compound heterozygous WISP3 gene mutation - Hou-De Zhou; Yan-Hong Bu; Yi-Qun Peng; Hui Xie; Min Wang; Lin-Qing Yuan; Yi Jiang; Duo Li; Qi-You Wei; Yu-Ling He; Tao Xiao; Jiang-Dong Ni; et al. (Journal of Molecular Medicine, 2007)

Assessment of genetic diversity in cultivars and wild accessions of Luohanguo (Siraitia grosvenorii [Swingle] A. M. Lu et Z. Y. Zhang), a species with edible and medicinal sweet fruits endemic to southern China, using RAPD and AFLP markers - Shao-Qing Tang; Xiao-Yun Bin; Yun-Tao Peng; Jun-Ya Zhou; Li Wang; Yang Zhong (Genetic Resources and Crop Evolution, 2007)

Genetic dissection of plant height by molecular markers using a population of recombinant inbred lines in maize - Tang Ji-hua; Teng Wen-tao; Yan Jian-bing; Ma Xi-qing; Meng Yi-jiang; Dai Jin-rui; Li Jian-Sheng (Euphytica, 2007)

Application of cDNA array for studying the gene expression profile of mature appressoria of Magnaporthe grisea - Qing-chao Jin; Hai-tao Dong; You-liang Peng; Bao-shan Chen; Jing Shao; Ye Deng; Cheng-en Dai; Yong-qi Fang; Yi-chun Lou; You-zhi Li; De-bao Li (Journal of Zhejiang University-SCIENCE B, 2007)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)